Numerical study of ammonia combustion in a drop tube furnace: Method evaluation and burnout air modification - Tao Zhang; Rui Tan; Tianxiang Ling; Jun Chen; Weidong Fan; Qian Wang (Fuel, 2027)

Alkali pretreatment enables enhanced levoglucosan production from catalytic pyrolysis of waste cellulose acetate - Hengbin Zhang; Rui Shan; Ying Liu; Chengyu Li; Jun Zhang; Haoran Yuan (Biomass and Bioenergy, 2027)

Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

In situ sludge reduction induced by graphene oxide: Mechanistic insights into metabolic uncoupling, maintenance energy and cryptic growth - Yaodong Wu; Yiqi Sun; Rui Yu; Yanan Cui; Fan Yang; Jun Li; Zehao Zhang (Bioresource Technology, 2026)

L-Arginine effectively alleviates doxorubicin-induced cardiac dysfunction by inhibiting myocardial fibrosis - Mo-li Zhu; Rui Hao; Meng-yao Zhao; Pei-yao Liu; Hong-dou Zhang; Peng Li; Ya-ling Yin; Hui-jun Liu; Guang-qiu Ren; Jie Zhang; Jing Yang (Molecular Biology Reports, 2026)

Astragaloside IV pretreatment enhances the therapeutic efficacy of bone marrow mesenchymal stem cells in murine fulminant hepatic failure - Ting-Ting Zhao; Wen-Qiang He; Rui-Zhi Shi; Bing-Yu Du; Mei-Mei Lan; Dan Zhou; Xiao-Qin Gao; Min Li; Jun-Feng Li; Li-Ting Zhang (Molecular Biology Reports, 2026)

Hypoxia-preconditioned bone marrow mesenchymal stem cells alleviate acute liver failure in association with the VEGF/c-Met pathway - Mei-Mei Lan; Rui-Zhi Shi; Zhe-Yu Li; Wen-Jun Qiao; Yong-Juan Guan; Wen-Qiang He; Jun-Feng Li; Li-Ting Zhang (Molecular Biology Reports, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Cuproptosis in hepatocellular carcinoma: bridging copper homeostasis with therapeutic horizons - Songsong Fan; Aoqing Wang; Rui Peng; Jun Cao; Daoyuan Tu; Bingbing Su; Jiahao Zhang; Shengjie Jin; Guoqing Jiang; Chi Zhang; Dou-Sheng Bai (Molecular Biology Reports, 2026)

Safety and efficacy of recombinant botulinum toxin type A (Eveotox®) in patients with post-stroke upper limb spasticity: Results from a Phase Ib/II clinical trial - Rongrong Lu; Lingjing Jin; Jianzhong Xiong; Lixin Zhang; Yaling Liu; Leilei Xu; Rui Wu; Jianhua Tang; Liandong Zhao; Lihua Dong; Weifeng Luo; Yu Pan; et al. (Toxicon, 2026)

Perfluorononanoic acid enhances non-small cell lung cancer progression through CD36-driven fatty acid metabolic reprogramming - Ce Qin; Jun Yuan; Rui Zhang; Li Liu; Yuesong Ban (Food and Chemical Toxicology, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Built-in electric field for synergistically regulating electronic structure and interfacial hydrogen-bond network toward ampere-level current anion exchange membrane water electrolysis - Yujie Liang; Xinyu Lao; Jiaying Zhang; Hao Feng; Rui Min; Jingjing Wang; Yingying Zheng; Jiaqi Pan; Chaorong Li; Jun Cao (Chemical Engineering Journal, 2026)

Optimization of zeolite configuration for enhanced aromatic formation during levoglucosan pyrolysis - Hengbin Zhang; Huiyu Liu; Rui Shan; Libin Wu; Ying Liu; Chengyu Li; Jun Zhang; Haoran Yuan (Biomass and Bioenergy, 2026)

In-situ engineered TiO2/Al2O3 photocatalytic membrane for water-vapor-assisted selective NO oxidation in coal-fired flue gas - Wenli Liu; Rui Hu; Chunyue Gao; Wenjuan Yang; Chang Li; Hui Chen; Zhicheng Zhang; Qingna Kong; Jun Yao; Yanbin Yun (Journal of Environmental Chemical Engineering, 2026)

Flow field fitting analysis of earth-rock dam leakage based on an image-based hybrid Quadtree-SBFEM - Binghan Xue; Yahao Bu; Shuaihao Su; Siye Zhang; Jianwei Lei; Rui Pang; Jun Liu (Journal of Applied Geophysics, 2026)

A biomimetic mineralized injectable hydrogel enables spatiotemporal dual-drug delivery for colorectal cancer therapy - Jing-Yu Feng; Rui Zhang; Jing-Ling Yang; Rui Lu; Kiran Thakur; Fei Hu; Yi-Long Ma; Jian-Guo Zhang; Zhao-Jun Wei (Chemical Engineering Journal, 2026)

Mechanistic insights into the adsorption and separation of nonpolar molecules on delocalization porous carbon: Dispersion interactions enhanced by multiple bonds - Peixin Wang; Jingxu Tian; Da Wei; Yue Sun; Bo Liu; Wenji Pi; Jun Ma; Yunfeng Zhang; Hongyu Chen; Rui Shi; Yang Guo; Xiang Xu; et al. (Chemical Engineering Journal, 2026)

Low-cost pillar-ligand engineering toward ultramicroporous MOFs for efficient SF6/N2 separation - Biao Fu; Hui-Ting Zheng; Rui-Ming Li; Duo Yue; Liang Song; Zhang-Wen Wei; Robert Langer; Mihail Barboiu; Ji-Jun Jiang; Cheng-Yong Su (Chemical Engineering Journal, 2026)

Schisandra chinensis polysaccharide attenuates diabetic islet cell injury by promoting autophagy via suppression of the PI3K/AKT/mTOR signaling cascade - Xiao-Ying Zhou; Guang-Hui Zhou; Wen-Chong Li; Jun-Feng Zhang; Ming-Kui Lin; Zi-Cong Liang; Rui-Ke Liu (Journal of Molecular Histology, 2026)

Interfacial electron redistribution stabilizes Cu-centered redox cycling for efficient Fenton-like catalysis - Xiao-Ying Li; Ruo-Lan Xu; Ren Zhu; Ting-Yu Zhang; Wen-Rui Wang; Wu-Jun Liu; Hong Jiang (Journal of Cleaner Production, 2026)

Toxic effects and molecular mechanisms of Fluopyram on the liver of zebrafish (Danio rerio) - Yuqing Hou; Bo Cheng; Baihui Shi; Shuhan Li; Xuzhi Zhang; Lanjun Wang; Rui Yang; Lusheng Zhu; Jun Wang; Young Mo Kim; Jinhua Wang (Journal of Environmental Management, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

Soil-specific resilience of comammox and canonical ammonia oxidizers shapes drought-heat legacy effects on N2O emissions - Shuoshuo Wu; Zhenhua Liang; Keyi Zhang; Jun Li; Baowei Hu; Guixin Chu; Rui Tao (Environmental Research, 2026)

Engineered probiotic carriers enregulate coordinated cuproptosis and ferroptosis with immune activation against bladder cancer - Anguo Zhao; Rongkang Li; Rui Liang; Qi Zhuang; Yang Liu; Dashi Deng; Peng Yu; Lei Peng; Hongbo Xu; Jun Zhang; Zhangxin He; Xin Chen; et al. (Chemical Engineering Journal, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Asymmetric atmospheric secondary circulation response to a sea surface submesoscale cold filament - Jun Yang; Ziqi Zhang; Jen-Ping Peng; Dongxiao Wang; Chunhua Qiu; Rui Shi; Mingming Shao; Shichang Zhao; Fei Yu; Yihua Luan (Science China Earth Sciences, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

Shifting the processing boundary: On-Farm Pulsed Electric Field Intervention (OFPI) for proactive bioburden reduction and functionalization of raw milk - Bing Yan; Lang-Hong Wang; Jin-Lin Cai; Xiao-Jun Zhang; Cai-Yun Wang; Jian Li; Rui Wang; Xin-An Zeng; Jian He (Trends in Food Science & Technology, 2026)

A novel AGTPBP1-ERK/MYLK network mediates pancreatic cancer progression - Zhe-yu Yang; Qian Zhang; Jing-rui Yang; Xiao-dong Zhang; Chang-le Liu; Jia-yu Huang; Rui Xiao; Jian-jun Ren (Tissue and Cell, 2026)

Towards Thermal Health Equity for Vulnerable Populations: Thermal comfort of pregnant women across gestational stages in hospital environments - Rui Guan; Jun Lu; Zhiang Zhang; Zhen Peng; Wu Deng; Paolo Beccarelli; Zhe Wang; Jinhao Zhang; Tong He; Siyu Ma (Sustainable Cities and Society, 2026)

Dimefluthrin-induced multigenerational endocrine toxicity in zebrafish (Danio rerio) offspring via parental exposure - Wei-Guo Wang; Rui-Rui Li; Ming-Jun Yang; Jing-Ying Hu; Wen-Ping Xu; Li-Ming Tao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

Enriched numerical manifold method with closed-form solutions for the crack-tip singularity in elastic fracture - Hua-rui ZHU; Hong ZHANG; Xi-long LI; Wei WU; Sun-jun HU; Gen-hua SHI (Computers and Geotechnics, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

Visible-light-driven N-CDs/Cu photocatalysis for CO2 valorization to selenylated vinyl oxazolidinones - Jun-Bo Wang; Jia-Tong Guo; Shu-Rui Wang; Bei Ruan; Zhan-Hui Zhang (Chemical Engineering Journal, 2026)

Correction to: Puerarin alleviates myocardial ischemia-reperfusion injury by enhancing FUNDC1-mediated mitophagy - Na Feng; Anhua Zhang; Lingling Yao; Jie Tang; Min Lu; Dandan Shi; Zhuoran Zhu; Rui Liu; Jun Chen; Xinwen Min; Handong Yang; Hao Xu; et al. (Molecular and Cellular Biochemistry, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Dexmedetomidine regulates fatty acid oxidation through the AMPK/PGC-1α/CPT1A pathway to mitigate renal ischaemia-reperfusion injury - Cong-Li Zhang; Yan Yan; Ke Wang; Jun-Jie Ma; Wen-Jun Xu; Gang Liu; Xing-Chun Zhu; Zhi-Gao Zhu; Hao-Feng Ding; Zi-Rui Ke; Kai Yao; Fang-Tian Fan; et al. (Toxicology and Applied Pharmacology, 2026)

Centralized mechanical e-waste dismantling is associated with lower farmland soil heavy metal pollution and carbon emission intensity - Yu Zhang; Ming-jiang He; Wei-jun Fu; Jie Wang; Ke-li Zhao; Xiang-rui Xu; Ji-zi Wu (Journal of Environmental Chemical Engineering, 2026)

Trends and coupling coordination of agricultural carbon effects and food security in the Yellow River Basin, China - Jiuran Nie; Lei Yu; Bingyao Zhang; Yu Li; Mo Li; Rui Jing; Liuyue He; Jun Wang; Yanlai Zhou (Journal of Cleaner Production, 2026)

Zircon U-Pb dating and geochemistry of the Paleoproterozoic tuffs from the Nsama formation in northeastern Zambia - Jun-ping Ren; A-lei Gu; Hong-wei Sun; Li-bo Zuo; Jie Wang; Bao-jin Zhao; Evaristo Kasumba; Shi Xing; Zi-jiang Liu; Jin-meng Dong; Jin-rui Zhang; Ji-hai Chen (Journal of African Earth Sciences, 2026)

Operation-resolved VOC emissions from electronics manufacturing: Implications for ozone formation, toxicity, and risk-oriented management - Jun Tao; Rui Xu; Zhisheng Zhang; Zijun Tang; Ping Fang; Leilei Fei; Zhihui Li; Zhihang Chen (Environmental Research, 2026)

Nanospike-enhanced synergistic disinfection of adsorption-puncture-oxidation for real wastewater reclamation - Rui Gao; Fang Huang; Jun Li; Yanmei Zhao; Zimeng Zhang; Boya Li; Jingni Xie; Aijie Wang; Shuhong Gao (Chemical Engineering Journal, 2026)

Macro- and micro-damage mechanism of cement-fly ash stabilized organic soil under freeze-thaw cycles - Jiling Zhao; Ping Yang; Dahu Rui; Jun Zhang; Xianwen Huang (Cold Regions Science and Technology, 2026)

Developmental light colour influences adult phototaxis and locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Zi-Yu Guo; Xu-Hui Guo; Sheng-Yu Hou; Ke-Jing Feng; Yu-Xin He; Han-Ning Wu; Xin-Hui Chen (Behavioural Processes, 2026)

Research on the Mechanisms Regulating Soil Microbial Community Structure and Functional Metabolism during Coloured Potato Cultivation with “Seed Rotation” - Yulong Wang; Anle He; Huachun Guo; Fang Yang; Youhan Li; Lei Bai; Jun Li; Rui Zhang (Potato Research, 2026)
To address the continuous cropping obstacles associated with coloured potatoes ( Solanum tuberosum L.) in the red soil region of Yunnan, in this study, two “seed rotation” cultivation regulation modes, namely cultivar rotation (red potato–purple potato) and crop rotation (red/purple potato–soybean), were innovatively proposed. Through pot experiments, the regulatory effects of different cultivation modes on soil nutrients, enzyme activities, microbial community structure, and functional metabolic networks were systematically analysed. Compared with the monocropping of a single potato cultivar, the cultivar switching treatment significantly improved the soil nutrient status, with the contents of soil available nitrogen, phosphorus, and potassium significantly increasing by 56.40–58.04%, 14.96–27.44%, and 58.59–62.21%, respectively, while the cultivar rotation treatment had a secondary effect. In addition, the interspecific rotation treatment enriched beneficial bacteria such as Bradyrhizobium ; upregulated the abundance of secondary metabolites, including flavonoids; and activated biosynthetic pathways such as those involving phenylpropanoids, flavonoids, and various amino acids. Compared with the continuous cultivation of a single potato cultivar, the cultivar rotation treatment alleviated the homogenization trend of the soil microbial community, increased the abundance of organic acids and glycosides, and activated pathways such as the shikimate pathway and the biosynthetic pathways of aromatic amino acids (phenylalanine and tyrosine). In summary, both modes, especially the interspecific rotation mode, can improve the soil environment and have significant agronomic application value and ecological environmental benefits. Owing to the similar biological characteristics between the same family, the cultivar rotation mode results in relatively limited changes in the soil microbial community and metabolite composition, but it can delay the occurrence of continuous cropping obstacles. This study provides practical value for the sustainable soil management of potato cultivation in red soil regions.

Quartz compositions decipher the source and magmatic-hydrothermal evolution of Himalayan LCT-type pegmatites - Yong-Neng Zhao; Jun-Xing Zhao; Noreen J. Evans; Chang-Tong He; Rui-Zhe Shi; Shen Gao; Li-Qun Zhu; Ke-Zhang Qin; Ming-Jian Cao (Mineralium Deposita, 2026)

Development and validation of a Mn/MOF-808 based colorimetric platform for rapid and reliable on-site monitoring of iodide in marine environments - Yi-Ting Chen; Xiao-Jun Dai; Xi- Qing Xu; Pei Liu; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Peng Wang; Chun-Hui Gong; Yi Yang (Analytica Chimica Acta, 2026)

TS_Predictor: a deep learning toolbox for GNSS time series prediction with signal decomposition and nonlinear modelling - Xiaoxing He; Yu Zhou; Jun Li; Gaël Kermarrec; Rui Fernandes; Jean-Philippe Montillet; Shuangcheng Zhang; Shunqiang Hu (Advances in Space Research, 2026)

Puerarin alleviates myocardial ischemia-reperfusion injury by enhancing FUNDC1-mediated mitophagy - Na Feng; Anhua Zhang; Lingling Yao; Jie Tang; Min Lu; Dandan Shi; Zhuoran Zhu; Rui Liu; Jun Chen; Xinwen Min; Handong Yang; Hao Xu; et al. (Molecular and Cellular Biochemistry, 2026)

Mode-Dependent optimal positioning of evacuation Guides: An Experimental–Modeling study on static and dynamic guidance effect - Weisong Liu; Jun Zhang; Rui Ba; Weiguo Song (Tunnelling and Underground Space Technology, 2026)

Bioactive edestin peptides from hemp (Cannabis sativa L.) seeds improve exercise performance under hypobaric hypoxia - Rui Zhang; Jie Liu; Liang-Liang Chen; Jia-Qi Liu; Xiao-Qian Jin; Zi-Xian Fu; Jun-Bin Xiong; Bin Jia; Jun-Ling Shi; Da-Chuan Yin (Food Research International, 2026)

Natural polysaccharide-modified oral pH-sensitive ZIF-8 delivery system for targeted release of lutein liposomes in the gastrointestinal tract - Lanxin Zhang; Shengnan Wang; Jingyi Long; Lina Yang; Jun Li; Lu Han; Rui Wang; Xiaohui Zhao; He Liu (Food Chemistry, 2026)

Structural features and antioxidant efficacy of a novel low-molecular-weight pectic polysaccharide from Fuzhuan brick tea - Xianbao Sun; Jun'ai Zhang; Rui Guo; Xuan Ma; Lihua Song; Yan Wu (Food Bioscience, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

High-efficiency lithium extraction from brine using molybdenum-doped lithium manganate in hybrid capacitive deionization - Qingqing Han; Jiahui Zhang; Zixiang Liao; Junhao Zhu; Youfang Zhang; Lei Wu; Rui Wang; Huanwen Wang; Yansheng Gong; Jun Jin (Chemical Engineering Journal, 2026)

Hydrothermal-responsive plasmonic aerogel for dynamic 3D hotspot regulation and ultrasensitive SERS detection of dairy products contaminants - Jing-Xiang Wang; Zhi-Gao Xu; Xin-Rui Wang; Yao-Yao Zhang; Ri-Hui Su; Xin-Xin Zhang; Su-Ming Dai; Wei-Wei Zhu; Xue-Cai Tan; Ke-Jing Huang; Jun Yan (Analytica Chimica Acta, 2026)

Macrophages with ITIH4 overexpression attenuate inflammatory responses and regulate intestinal epithelial cells - Jing Li; Zhuoqi Zhao; Jun Fei; Rui Zhang; Liya Pan; Ying Xiang; Li Hong; Zhiyan Zhan (Inflammation Research, 2026)

Integrated metabolomics and transcriptomics analyses provide insights into flavor and color regulation during tomato postharvest ripening - Xian-Kang Xiao; Wei-Xin Liu; Xiao Lu; Cai-Rui Chen; Xin-Yi Zhang; Xiao-Jun Pu; Feng Wang (Postharvest Biology and Technology, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Phosphogypsum coupled enzyme-induced calcium carbonate precipitation for soil stabilization: Mechanical performance and sustainable application - Lun Zhang; Yun Dai; Zhenyao Xia; Jun Wu; Zhien Zhu; Yunkang Rao; Hongqiang Shi; Chao Kang; Rui Xiang; Hongwei Guo; Hai Xiao (Journal of Environmental Management, 2026)

Self-assembled 8-shogaol/curcumin nanoparticles via hydrogen bonding: enhanced stability and sustained release in vitro - Rui Zhang; Jing-Yu Feng; Kiran Thakur; Fei Hu; Jian-Guo Zhang; Yi-Long Ma; Zhao-Jun Wei (Food Chemistry, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Dual-phase Co/CoFe nanoparticles anchored on N, F co-doped hollow carbon microcapsules as efficient bifunctional catalysts for aqueous/quasi-solid-state Zn-air batteries - Bin Cui; Yunfeng Zhu; Xingyue Fang; Renjing Du; Jiabao Bai; Mengran Li; Wanting Xiang; Wenxuan Xie; Yana Liu; Jiguang Zhang; Rui Shi; Jun Wang; et al. (Chemical Engineering Journal, 2026)

Sn2+ doping-induced activation of inert adsorption sites in Li/Al-LDHs for selective lithium extraction from brines - Rui Zhang; Chenlu Yan; Jun Chen; Ting Wei; Jianguo Yu; Sen Lin (Chemical Engineering Journal, 2026)

Integrative Analysis the Role of ENG as a Metabolic and Macrophage-Related Gene in Hepatocellular Carcinoma - Songsong Fan; Yuhong Tang; Jun Cao; Rui Peng; Bingbing Su; Daoyuan Tu; Weidi Yu; Chen Chen; Shunyi Wang; Shengjie Jin; Guoqing Jiang; Chi Zhang; et al. (Biochemical Genetics, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Ferrate-assisted nonthermal plasma for efficient PFOA degradation in landfill leachate: Mitigating bulk organic interference and enhancing application potential - Changtao Chen; Zhuofan Yu; Rui Zhang; Xuetong Yang; Qintong Wang; Yuxian Ji; Xiaoyu Cheng; Jun Li; Anton Nikiforov; Stijn W.H. Van Hulle; Bo Lai (Water Research, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Endoplasmic reticulum stress-induced CHOP activation mediates NLRP3 inflammasome-dependent pyroptosis in BDE-47-induced cognitive dysfunction - Quan Yuan; Rui Zhang; Jun Hu; Siman Lin; Ying Zhu; Junhong Geng; Ge Du; Xiao Yang; Yipin Zhao; Dongmei Wang; Binbin Wang; Hua Fan (NeuroToxicology, 2026)

Construction and textural modification of soft surimi gel from spanish mackerel (Scomberomorus niphonius) by polysaccharides - Yin-Yin Lv; Xian-Hao Zhang; Jia-Ni Zhou; Ying-Rui Wang; Zhu-Jun Zhang; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2026)

Synergistic control of Pseudomonas aeruginosa by LAB and phage for sustainable aquatic preservation - Siming Xue; Kairui Zhao; Rui Dong; Haichen Li; Ruizi Wang; Wei Cheng; Yuqi Fan; Qin Zhang; Ziyi Xue; Yujin Wu; Jun Zhang; Yanmei Sun; et al. (Food Bioscience, 2026)

Environmental stress and symbiotic shifts: The impact of perfluorooctanoic acid (PFOA) on soil microbe-plant networks - Zhan Chen; Jiajie Lou; Mengyao Yan; Rui Cui; Yicheng Jin; Mengwei Zhang; Rongshe Zhang; Shuduan Mao; Jun Chen; Liwei Sun; Tao Lu; Haifeng Qian (Environmental Pollution, 2026)

Enhanced aromatics production from cassava residue pyrolysis via optimizing zeolite configuration - Jun Zhang; Yilun Shui; Huiyu Liu; Rui Shan; Chengyu Li; Haoran Yuan; Yong Chen (Bioresource Technology, 2026)

Zinc finger protein ZNF638 in brown fat deteriorates type 1 diabetes via retinol binding protein 4 - Meiyao Meng; Shuang Liu; Yinzhao Zhong; Jingyi Hu; Lijun Zhu; Jin Qiu; Rui Wang; Yuan Luo; Yingwen Wang; Wenhao Zhou; Guangyu Shan; Zhenyu Du; et al. (Science Bulletin, 2026)

Ginkgonins A and B: Two new sesquiterpenoids from Streptomyces ginkgonis TH01 - Yun-Fei He; Jing Miao; Chao Jian; Rui-Jun Wang; Yong-Sheng Gao; Jie-Hao Jin; Xiao-Yi Chen; Ji-Dong Wang; Shao-Yong Zhang (Phytochemistry Letters, 2026)

Plant protoberberine alkaloids: structural diversity, biosynthesis, synthesis, biological activity, structure-activity relationships and clinical applications of berberine - Weiqi Jiang; Wen Zhang; Chenxin Jing; Han Zhou; Zhi-Jun Zhang; Rui Wang; Ying-Qian Liu (Phytochemistry, 2026)

Soil organic matter revisited: Why humic substances still matter? - Sen DOU; Yifeng ZHANG; Jun SHAN; Meng WU; Rui MA; Song GUAN; Zhongjun JIA (Pedosphere, 2026)

Dual-function Ag2O/Zn-hemin MOF composites for radioactive iodide: performance and mechanism studies for removal and efficient visual detection - Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Man-Li He; Kai Chen; Yan Jiao; Peng Wang; Chun-Hui Gong; Yi Yang (Environmental Research, 2026)

Advances in three-dimensional fish cell models for aquatic toxicology - Ping-Ping Zhang; Chong-Rui Yao; Wen-Jun Shi; Ting Xu; Guang-Guo Ying (Aquatic Toxicology, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Spatial and seasonal variation in bioturbation potential of Macrobenthic communities in Bohai Bay - Yifeng Shi; Wenzhe Xu; Rui Gu; Wenxin Zhou; Guicheng Zhang; Yu Guo; Yiyan Guo; Jun Sun (Progress in Oceanography, 2026)

Lutein liposomes for enhancing lutein delivery stabilized by stigmasterol: Preparation, characterization and release in vitro - Lanxin Zhang; Shengnan Wang; Xinhong Liu; Jun Li; Rui Wang; He Liu (Journal of Food Engineering, 2026)

Green Intelligent Fertilizer derived from yellow phosphorus slag boosts rice yield and mitigate environmental impacts in high-altitude watersheds - Suoqian Kang; Ou Yu; Shuntao Zhang; Yujiao Tan; Rui Wang; Xueli Du; Jun Cao; Zhong Duan; Fei Huang; Rong Li; Changzhou Wei; Jiujiang Xu (Field Crops Research, 2026)

Influence of coal dust on flame propagation characteristics and spectral features of gas explosion - Qiuhong Wang; Zezhou Song; Jun Deng; Zhenmin Luo; Wei Gao; Yating Zhang; Guoqiang Dong; Rui Guo; Di Wu (Chemical Engineering Journal, 2026)

Effect of freeze-thaw cycle on biochar-stabilized heavy metal contaminated soils: A comparative analysis in seasonally frozen regions with and without groundwater recharge - Jun Zhang; Zhijun Zhang; Jiangshan Li; Dahu Rui; Lianli Xu; Guoyu Li (Cold Regions Science and Technology, 2026)

Genome-wide analysis of the sugarcane SUT gene family reveals ShSUT4 as a key regulator of abiotic stress responses - Xue-Ting Zhao; Ahmad Ali; Cui-Lian Feng; Ji-Shan Lin; Rui-Jie Wu; Shu-Zhen Zhang; Guang-Run Yu; Hai-Feng Jia; Yu-Qing Gong; Ting-Ting Zhao; Jun-Gang Wang (Theoretical and Applied Genetics, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Variations in C:N:P Stoichiometry, Non-Structural Carbohydrate, Chlorophyll, and Hormones of Abelmoschus manihot Flower at Different Phenological Growth Stages - Wen-zhang Qian; Hong-rui Wang; Shao-jun Fan; Yi-xiao Xiao; Yun-yi Hu; Guo-xing Cao; Shun Gao (Journal of Plant Growth Regulation, 2025)

Advanced design for nonlinear photovoltaic system problems: A co-evolutionary framework based on a decomposition approach - Yujun Zhang; Wenyin Gong; Rui Zhong; Huiling Chen; Jun Yu; Junbo Jacob Lian; Juan Zhao; Zhengming Gao (Swarm and Evolutionary Computation, 2025)

Highly selective electrocatalytic CO2 reduction to formate by a dinuclear nickel complex: cooperative catalysis across diverse conditions - Haitao Lei; Fengwang Li; Chengyu Liu; Jun Li; Yabo Wang; Dae-Hyun Nam; Yanwei Lum; Si-Xuan Guo; Yi Xu; Jie Zhang; Wenzhen Lai; Rui Cao (Science Bulletin, 2025)

Dynamic characteristics of a novel floating offshore photovoltaic system with flexible rope-net connection - De-Qing Zhang; Hong-Wei Tian; Zhi-Ming Yuan; Shuang-Rui Yu; Jun-Feng Du; Hua-Jun Li (Ocean Engineering, 2025)

Tailored SO2 capture in multivariate UiO-66(Zr) MOFs: Experimental insights and theoretical mechanisms - Zai-Dong Shao; Peng Wu; Fang Liu; Qi-Jun Zhang; Chao-Yang Guo; Rui-Sang Liu; Jiang Lu; Xiao-Meng Ren; Yu-Ming Zheng (Journal of Environmental Chemical Engineering, 2025)

Insights into the combined effect of N2H4 and NH2OH on CANON process in SBR: Nitrogen removal performance, stability of process and microbial community - Zi-Yue Li; Run-Mei Li; Xin Ma; Jia-Min Zhou; Ying-Jun Sun; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Zi-Jun Yan; Qian-Qian Zhang; Zai-Yong Zhang (Journal of Environmental Chemical Engineering, 2025)

Chemical constituents of Tinospora hainanensis and their chemotaxonomic significance - Ming-Hua Wang; Rui Ao; Bao-Qiang Liu; Juan Zhang; Jun-Sheng Zhang (Biochemical Systematics and Ecology, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Transcriptomic analysis of the mechanism of male reproductive injuries caused by the mixture of three phthalates in rats - Ling-Zi Xia; Jun-Zhe Yue; Li-Jun Wu; Qian-Ying Jin; Yi-Pei Yang; Jing-Yang Yu; Rui-Zhe Pan; Xin Zhang; Xiao-Ying Wu; Jiayin Zhu; Hai-Tao Gao (Toxicology and Applied Pharmacology, 2025)

Frititaipaines A−O, undescribed cevanine-type isosteroidal alkaloids from the bulbs of Fritillaria taipaiensis and their anti-neuroinflammatory and AChE inhibitory activities - Zai-Long Huang; En-Ke Qu; Lan-Run Yang; Rui Luo; Yan-Ni Liang; Shi-Jun Liu; Yuan-Zhen Xu; Dong-Bo Zhang (Phytochemistry, 2025)

Eugenol-based meroterpenoids with neural differentiation activity from Eugenia caryophyllata - Cong Yan; Sheng-Rui Yan; Yutong Zhu; Mengjiao Cai; Rui-Li Huang; Xinyu Wang; Shiqing Zhang; Lei Shi; Li-Jun Hu; Wen-Cai Ye; Xiao-Jun Huang; Ying Wang; et al. (Phytochemistry, 2025)

Deep learning approach for internal tide prediction based on China Ocean Reanalysis data - Rui Su; Jun Zhao; Senliang Bao; Hongli Fu; Huizan Wang; Xiaojiang Zhang; Xiang Wang; Can Ma; Weimin Zhang; Xinrong Wu (Ocean Engineering, 2025)

Discovery of ca. 2.33–2.22 Ga magmatic activities in the Longshan Complex bordering the southwestern margin of the North China Craton: Implications for tectonic transformation - Yi-Yi Zhang; Jun-Sheng Lu; Rui-Ying Zhang; Yu-Ting Li; Xu Kong; Gang Liu; Qiang Feng; Zeng-Yin Duan; Juan-Juan Li (Lithos, 2025)

The potential of anthraquinone-2-sulfonate (AQS) for “shell breaking” of iron-coated denitrification granular sludge - Xin-Rui Zhang; Zhi-Han Xi; Zi-Jun Yan; Xin-Tao Liu; Ying Wang; Run-Mei Li; Zi-Yue Li; Ke-Yu Wu; Ren-Cun Jin; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Management, 2025)

A carrier-assisted strategy for accelerating aerobic granulation under low superficial gas velocity: Critical contributions of sediment biochar and camellia shell biochar carriers - Qingxia Lin; Chuxuan Song; Jun Li; Ziqiang Liu; Xue Hu; Rui Xue; Suiqin Yang; Yang Gao; Wei Zhang; Lean Zhou; Julong Sun; Jinting Wang; et al. (Environmental Research, 2025)

Laboratory characterization of VOC evaporative emissions from light-duty plug-in hybrid electric vehicles: Environmental impact comparison with conventional vehicles - Ling Li; Rui Yuan; Wei Hu; Hualong Xu; Pingjiang Lv; Qin Xu; Jun Wang; Xue Jiang; Jianxun Tan; Jianli Yin; Zhenliang Li; Dan Zhang (Environmental Pollution, 2025)

Optimizing lithium extraction from brines using fluoride-doped lithium titanate in hybrid capacitive deionization - Jiahui Zhang; Wen Xi; Jianing Hu; Qingqing Han; Youfang Zhang; Shuo Huang; Rui Wang; Huanwen Wang; Yansheng Gong; Jun Jin (Desalination, 2025)

Dual-stage reverse-dialysis-engineered cartilage-biomimetic hydrogels: Highly resilient anti-swelling double-layer architectures - Zheng-Feng Zhang; Mei-Yan Ling; Xiao-Rui Ge; Jia-Ying Chen; Bei Zhang; Xiao-Hui Yao; Peng Song; Wei-Guo Zhao; Dong-Yang Zhang; Jun Wang (Chemical Engineering Journal, 2025)

Mitochondria-targeted piezoelectric catalyst regulate pyroptosis and efferocytosis for enhancing the osteosarcoma immunogenic death - Linbang Wang; Rui Dou; Yunlong Ma; Jiayu Zhang; Xiaomeng Cai; Jinkun Liu; Xiaoguang Liu; Jun Chen (Chemical Engineering Journal, 2025)

Thermodynamic and kinetic improvement of MgH2 via the synergism of Al species and Nb-TiO2 - Mengran Li; Jialing Gu; Qinke Tang; Jiabao Bai; Bin Cui; Ruoyu Ma; Yunfeng Zhu; Rui Shi; Yao Zhang; Jiguang Zhang; Yana Liu; Jun Wang; et al. (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Timosaponin B- II Enhances Osteogenic Differentiation of Human Periodontal Ligament Stem Cells via PI3K/AKT/GSK3β Signaling Pathway - Dai-Wei Yang; Xiao-Bin Cui; Rui Dong; Zhao-Yan Wu; Yu-Xing Zhang; Peng Yang; Jun Zhang (Stem Cell Reviews and Reports, 2025)

Prolonged sepsis triggers abnormal mitochondrial dynamics in the limb muscles and diaphragm - Chao Xiong; Fasheng Guan; Jianguo Feng; Jing Jia; Jumei Zhang; Rui Tu; Jie Li; Jun Zhou; Jianglin Wang; Li Liu (Molecular and Cellular Biochemistry, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Mechanistic insights into Perfluorooctanoic acid (PFOA) and Perfluorooctane sulfonates (PFOS)-induced nitrification acceleration: Interkingdom collaboration of AOA-comammox in calcareous soils - Shuoshuo Wu; Keyi Zhang; Yuehang Zhu; Luo Zhang; Wangying Ding; Jun Li; Baowei Hu; Guixin Chu; Rui Tao (Journal of Hazardous Materials, 2025)

Pt/Ca bimetallic-modified N-doped carbon for selective conversion of furfural into 1,2-pentanediol - Huiyu Liu; Ying Qiu; Rui Shan; Jun Zhang; Haoran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

The relationship between anaerobic oxidation of methane and dark carbon fixation in methane seep sediments - Yinan Deng; Rui Xie; Qingjun Guo; Shengxiong Yang; Ganglan Zhang; Hongfei Lai; Qianyong Liang; Fang Chen; Jun Cao (Global and Planetary Change, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Synthesis of confined palladium nanocatalysts in crystalline hemoglobin framework: An ultrastable nanoreactor for Cr(VI) detoxification - Xiao-Qian Jin; Jia-Lei Li; Jun-Bin Xiong; Rui Zhang; Chen-Yuan Li; Xue-Ting Wang; Wei-Hong Guo; Da-Chuan Yin (Environmental Research, 2025)

Self-feedback cascading DNA circuit encapsulated within a gene-modified bifunctional virus-inspired nanovector for light-gated spatiotemporal biosensing in live organisms - Xiao-Xue Chen; Yong-Yao Song; Zhuo Chen; Tian-Tian Zhang; Wei-Lin Chen; Xiao-Mei Wang; Jun-Rui Hu; Cheng-Yu Li (Analytica Chimica Acta, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Genome-wide association and epidemiological evidence linking air pollution to aging mechanisms - Xiao-Yu Liu; Dong Peng; Xu-Rui Liu; Yuan-Hui Sheng; Jun-Nan Zhao; Rong-Bin Xu; Dan Zhang; Bo Chen (Journal of Hazardous Materials, 2025)

Ionic liquid modified MOF-808 for efficient adsorption and stable capture of radioactive iodine - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Wen-Rui Zhang; Xiang-Hua Qi; Chun-Hui Gong; Peng Wang; Man-Li He; Yi Yang (Journal of Environmental Management, 2025)

Catalytic pyrolysis of polyethylene over bimetallic-modified ZSM-5: Role of alkaline sites on structure regulation, thermal behavior and aromatics production - Huiyu Liu; Ying Qiu; Rui Shan; Jun Zhang; Haoran Yuan; Yong Chen (Fuel, 2025)

Co-culture yeast driving fermentation of Litchi (Litchi chinensis Sonn.) seed vinegar: flavor synergistic regulation and flavonoid enrichment mechanism - Yizhuo Zhang; Jun Huang; Rongqing Zhou; Suyi Zhang; Yong Li; Rui Huang; Rui Liu; Chongde Wu (Food Bioscience, 2025)

Unprecedented triterpenes with anti-inflammatory activity from Limax maximus - Ya-feng Wang; Pei-de Tang; Rui-jie He; Zhang-bin Liu; Yong-qiong Wei; Jun Ruan; Bing-yuan Yang; Yong-lin Huang (Journal of Natural Medicines, 2025)

Using Interactive Multi-Media Panorama Virtual Reality to Balance Heritage Science, Education and Conservation At Zhoukoudian, Fangshan UNESCO Global Geopark - Jun-Ting Qiu; Tong-Yu Zhang; Lixian Tian; Xin-Min Rui; Hong-Xu Mu; Liang Qiu; Long-Xin Xu (Geoheritage, 2025)

Intelligent Alignment Control for Floating Raft Air Spring Mounting System Under Coupled Hull–Raft Deformation - Jian-Wei Cheng; Wen-Jun Bu; Ze-Chao Hu; Jun-Qiang Fu; Hong-Rui Zhang; Liang Shi (Journal of Marine Science and Engineering, 2025)
Shaft alignment is adversely affected by the increasingly severe coupled hull–raft deformation in deep-diving, highly integrated submersibles, thereby compromising operational safety and potentially amplifying vibration noise. To address to this issue, this paper investigates an intelligent alignment control method for the floating raft air spring mounting system (ASMS) applied to marine propulsion unit (MPU) under coupled hull–raft deformation conditions. A multi-objective alignment control algorithm was developed based on the NSGA-II optimization method within an N-step receding horizon optimal control framework, enabling simultaneous achievement of shaft alignment attitude adjustment, hull deformation compensation, raft deformation suppression, and pneumatic energy consumption. Experimental validation was conducted on two distinct ASMS prototypes to evaluate the control algorithm. Tests performed on the ASMS for MPU (MPU-ASMS) prototype demonstrated effective compensation of hull-induced deformations, maintaining shaft alignment offsets within ±0.3 mm and angularities within ±0.5 mm/m. Concurrently, experiments on the floating raft ASMS for the stern compartment (SC-FR-ASMS) achieved precise control of axial offsets within ±0.3 mm, angularities within ±0.5 mm/m, and vertical displacements of critical monitoring points within ±1 mm. The adaptive control strategy additionally proved effective in suppressing raft deformation while simultaneously optimizing pneumatic energy consumption. This research provides robust theoretical and technical foundations for intelligent vibration isolation systems in deep-sea equipment to accommodate extreme-depth-induced hull deformation and large-scale raft deformation.

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Removal of disinfection residual bacteria in UV222, UV222/H2O2 and UV222/peroxymonosulfate systems: what is the safe usage for wastewater reclamation - Rui Gao; Shu-Hong Gao; Jun Li; Fang Huang; Yanmei Zhao; Jingni Xie; Yusheng Pan; Wanying Zhang; Aijie Wang (Water Research, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

Predicting estrogen receptor agonists from plastic additives across various aquatic-related species using machine learning and AlphaFold2 - Wen-Jun Shi; Zhou Cao; Xiao-Bing Long; Chong-Rui Yao; Jin-Ge Zhang; Chang-Er Chen; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

FlashSim: A novel particle-in-cell numerical model for vacuum surface flashover simulation based on finite element method - Hao-Yan Liu; Guang-Yu Sun; Yue-Lin Liu; Shu Zhang; Chang-Chun Qi; Sheng Zhou; Wen-Rui Li; Guan-Jun Zhang (Computer Physics Communications, 2025)

Assessment of Thermal Vulnerability and Analysis of Influencing Factors in Urban Functional Areas of Foshan City, China - Xinyue Wang; Jun Yang; Rui Zhang; Jiaxing Xin; Wenbo Yu; Jiayi Ren; Xiangming Xiao (Chinese Geographical Science, 2025)

Modulating expression of Frankliniella occidentalis glutathione S-transferase genes to adapt to host shifts - Tao Zhang; Li Liu; Ding-Yin Li; Wen-Bo Yue; Guang Zeng; Dan Zhou; Jun-Rui Zhi (Arthropod-Plant Interactions, 2025)

Parapedobacter flavus sp. nov., isolated from padding of fermentation bed - Rui Wang; Yan-Yan Zheng; Zi-Xuan Liu; Xuan Zhang; You-Jun Liao; Ya-Jing Yu; Ai-Hua Li (Antonie van Leeuwenhoek, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Bipartite trophic levels cannot resist the interference of microplastics: A case study of submerged macrophytes and snail - Jun Chen; Zhiqiang Zhang; Nan Shen; Hongwei Yu; Guo Yu; Jing Qi; Rui Liu; Chengzhi Hu; Jiuhui Qu (Journal of Hazardous Materials, 2025)

Flexural behavior of reinforced concrete beams subjected to natural corrosion in marine environment - Yang Liu; Wei-Ping Zhang; Chao Jiang; Feng Wu; Jun-Li Qiu; Rui-Lin Wang; Nai-Hao Zheng (Engineering Structures, 2025)

Multifunctional amine salt additive for enhancing the performance of perovskite and perovskite/silicon tandem solar cells - Jun Qu; Wenfeng Zhang; Yangdi Chen; Huiyao Zhao; Yanbei Wei; Rui Zhou; Hongjie Wan; Jie Deng; Dongyong Fan; Yuchen Luo; Haijin Li (Chemical Engineering Journal, 2025)

Mangiferin promotes porcine oocyte maturation and delays the postovulatory aging process by up-regulating NRF2 levels - Xiuwen Yuan; Hewei Ji; Yuhao Zhang; Huilin Peng; Neng-hao Cao; Jia-jun Ren; Xue-rui Yao; Xingwei Liang; Nam-hyung Kim; Yong-nan Xu; Ying-hua Li (Theriogenology, 2025)

Remediation of a Pb and Cd-contaminated clayey soil via magnetic-enhanced washing - Dahu RUI; Yuru WANG; Wenjun NIE; Mintae KIM; Jun ZHANG; Shuren WANG; Yuzuru ITO; Fujun NIU (Pedosphere, 2025)

Enhanced gut damage and microbial imbalance in bullfrog tadpoles (Lithobates catesbeiana) exposed to polystyrene microplastics under high-temperature conditions - Zhilong Wang; Jun Xie; Guangjun Wang; Huirong Yang; Zhifei Li; Kai Zhang; Rui Shu; Wenping Xie; Jingjing Tian; Hongyan Li; Wangbao Gong; Yun Xia (Environmental Pollution, 2025)

Highly selective and reversible adsorption of trace gaseous ammonia by a stable nanoporous carboxylic acid-functionalized silica aerogel - Zai-Dong Shao; Ting-Ting Hu; J. Paul Chen; Qi-Jun Zhang; Peng Wu; Rui-Sang Liu; Jiang Lu; Xiao-Meng Ren; Yu-Ming Zheng (Chemical Engineering Journal, 2025)

Solid-state fermentation of distillers grains with Aspergillus pachycristatus for echinocandin B biosynthesis - Jiaxin Tang; Weibing Zhang; Jing Xu; Luyan Sun; Yaqi Dang; Haoyang Li; Liyan Yu; Jing Su; Ting Xue; Rui Guo; Jun Xie; Lei Wang (Bioresource Technology, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Systemic resistance of kidney bean plants induced by exogenous CaCl2 and western flower thrips infestation - Guang Zeng; Jun-Rui Zhi; Tao Zhang; Wen-Bo Yue; Ding-Yin Li; Mao Ye (Arthropod-Plant Interactions, 2025)

Ecological security and structural optimization of land space in the Pearl River Delta Urban Agglomeration: an approach based on the footprint family - Cong Huang; Jun Liu; Hanyu Yin; Zhonghao Zhang; Wei Cao; Wenfang Tan; Xufeng Fei; Chen Xu; Lumeng Liu; Jiali Chen; Kai Li; Rui Xiao (Environment, Development and Sustainability, 2025)

Growth monitoring of rapeseed seedlings in multiple growth stages based on low-altitude remote sensing and semantic segmentation - Fanguo Zeng; Rui Wang; Youming Jiang; Zhendong Liu; Youchun Ding; Wanjing Dong; Chunbao Xu; Dongjing Zhang; Jun Wang (Computers and Electronics in Agriculture, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Fabrication of flexible polymer-MOF composite electrolyte for solid-state lithium metal batteries with high rate performance - Jiansheng Gao; Yan Chai; Jialun Ni; Yong Zeng; Gaoyuan Zhang; Xueling Liu; De Ning; Xinghui Jin; Huajun Zhao; Dong Zhou; Rui Gao; Wei Wu; et al. (Chemical Engineering Journal, 2025)

Graphene oxide/Ni/carbon nanocoils synergizing dielectric/magnetic/chiral multiple losses for weather-resistant electromagnetic protective application - Haiming Lv; Lihong Wu; Changlong Du; Gengping Wan; Jun Liu; Pengpeng Mou; Rui Liu; Hualin Xiong; Mingnan Zhang; Guizhen Wang (Chemical Engineering Journal, 2025)

Study on freeze-thaw resistance and Na+ leaching characteristics of red mud-fly ash-phosphogypsum multiple solid waste road base material - Shengjie Liu; Dahu Rui; Mintae Kim; MingChang Ji; Jun Zhang; Pengfei Zhang (Cold Regions Science and Technology, 2025)

Multivariable integrated risk and spatiotemporal characteristics assessment for water quality using comprehensive risk index in Jiangsu section of the south-to-north water diversion project, China - Yue Zhang; Jun Hou; Rui Zhou; Jun Lu; Jun Xia; Jun Wu; Guoxiang You; Zijun Yang; Lingzhan Miao (Environmental Geochemistry and Health, 2025)

Evaluating the Centre‐Periphery Hypothesis Through Genomic Phylogeographical Comparisons of Two Sister Species of Liquidambar in East Asia's Tertiary Relict Forests - Tian‐Rui Wang; Wu‐Qin Xu; Hans‐Peter Comes; Xin‐Yi Zhang; Jun Chen; Yin‐Gang Li; Ying‐Xiong Qiu (Journal of Biogeography, 2025)
Aim Understanding the spatial distribution of genetic variation within species is a central tenet in evolutionary biology and conservation biology. This study explores how historical demographic processes and/or environmental factors interact to affect contemporary genetic variation and adaptive potential, with a specific focus on testing the ‘centre‐periphery’ hypothesis (CPH). Location Subtropical China. Taxon Liquidambar. Methods We combined comparative phylogeography, landscape genomics and niche modelling to investigate the interplay between demographic history and past/current environmental factors in shaping genetic variation in Liquidambar formosana and L. acalycina , a sister pair of East Asia's Tertiary relict forests. Results In both species, core populations occupied highly suitable habitats at highest densities. Consistent with the CPH, population genetic diversity decreased, and differentiation increased, from centre to margin in L. acalycina , but not in L. formosana , likely reflecting different demographic histories and different relative contributions of geography, past (LGM) and current climates to their present‐day genetic variation. In addition, L. formosana showed higher adaptive potential to future climate change than L. acalycina . Main Conclusions This study demonstrates that differences in contemporary genetic variation and adaptability among closely related species can be explained by contrasting demographic responses to multiple geographic/climatic factors. In turn, it should also expand our understanding of the CPH, while informing future conservation efforts for these two study species.

Promotional role of Ru in bimetallic catalysts for selective transfer hydrogenation of bio-based furfural - Yaoxin Xiao; Yazhuo Wang; Jun Zhang; Gangqi Cheng; Dong Liang; Rui Shan; Haoran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

High performance Ni-MgO (111) nanosheet catalysts for CO2 reforming with methane - Xirui Yan; Rui Wang; Fen Yue; Ruicong Wang; Huigang Zhang; Jun Li; Wencai Peng; Jinli Zhang (Fuel, 2025)

The research on the synergistic improvement of water retention capacity and eating quality of marinated pork meat by the combination of basic arginine and acidic aspartic acid - Kuo Xu; Ao-Jing Lv; Rui-Ling Dong; Yu-Cong Li; Li-Ting Zeng; Yang Wang; He-Shuai Li; Jun Qi; Hu-Hu Wang; Chun-Hui Zhang; Guo-Yuan Xiong; Qing-Yong Zhang (Food Chemistry, 2025)

Atomically dispersed dual-active-site catalyst for enhanced oxygen reduction reaction: Synergistic effect of Fe and V in M−N−C structures - Qi-Dong Ruan; Rui Feng; Lu Liu; Lu Zhang; Jiu-Ju Feng; Yacheng Shi; Yi-Jing Gao; Ai-Jun Wang (Chemical Engineering Journal, 2025)

The truncated AXIN1 isoform promotes hepatocellular carcinoma metastasis through SRSF9-mediated exon 9 skipping - Qian-qian Zhang; Ying-shuang Miao; Jun-yi Hu; Rui-xuan Liu; Yue-xiao Hu; Feng Wang (Molecular and Cellular Biochemistry, 2025)

Targeting ferroptosis for the treatment of female reproductive system disorders - Rui Ye; Yi-ming Mao; Yi-ran Fei; Yue Shang; Ting zhang; Zhe-zhong Zhang; Yong-lin Liu; Jun-yu Li; Shi-liang Chen; Yi-bo He (Journal of Molecular Medicine, 2025)

Effects of alternating wet and dry irrigation regimes on rice growth and physiology characteristics in southeast China - Rui Zhou; Haofang Yan; Chuan Zhang; Xingye Zhu; Guoqing Wang; Bin He; Kinda Negessa Disasa; Imran Ali Lakhiar; Run Xue; Yudong Zhou; Biyu Wang; Jun Li; et al. (Paddy and Water Environment, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

A small RNA effector conserved in herbivore insects suppresses host plant defense by cross-kingdom gene silencing - Wen-Hao Han; Shun-Xia Ji; Feng-Bin Zhang; Hong-Da Song; Jun-Xia Wang; Xiao-Ping Fan; Rui Xie; Shu-Sheng Liu; Xiao-Wei Wang (Molecular Plant, 2025)

Effectively enhanced hydrogen storage properties of Mg90Al10 catalyzed by CeF3 - Mengran Li; Qinke Tang; Lili Yang; Rui Shi; Shihao Chen; Yingzhen Zhu; Yunfeng Zhu; Yao Zhang; Jiguang Zhang; Yana Liu; Jun Wang; Zhixin Ba (Fuel, 2025)

Environmentally relevant concentrations of DBDPE (decabromodiphenyl ethane) induce intestinal toxicity in silkworms (Bombyx mori L.) - Xue Luo; Rui Xing; Man Xu; Hui-Jun Jiang; Yu-Rui Wang; Ming-Yue Hu; Hao Zhang; Feng Ge; Wei Zhang; Hong-Wei Wang (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

The Impact of Different Mating Systems on Locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Ruo-Xi Wang; Jia-Xin Xu; Kai-Chen Weng; An-Xin Wang; Hao Huang; Yu-Yuan Lu; Yi-Jie Chen; Yu-Chen Wang (Journal of Insect Behavior, 2025)

Selenium Treatment Alleviates the Inhibition Caused by Nep-L Gene Knockdown in Silkworm (Bombyx mori) - Ting-Ting Hong; Fei Hu; Wen-Jie Ge; Rui Zhang; Juan Du; Kiran Thakur; Shun-Ming Tang; Zhao-Jun Wei (Biological Trace Element Research, 2025)

Sequential decline in cyanobacterial, total prokaryotic, and eukaryotic responses to backward flow in a river connected to Lake Taihu - Jun Zuo; Siyu Yang; Hans-Peter Grossart; Peng Xiao; He Zhang; Rui Sun; Guoyou Li; Haoran Jiang; Qihang Zhao; Meng Jiao; Yao Cheng; Zeshuang Wang; et al. (Water Research, 2025)

Berbamine inhibits Pseudorabies virus in vitro and in vivo - Liang Li; Muze Lv; Yangfan Li; Huihui Sun; Jie Li; Wenyan Li; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jun Wang; et al. (Veterinary Microbiology, 2025)

Corrigendum to “Differentiation of sow and mouse ovarian granulosa cells exposed to zearalenone in vitro using RNA-seq gene expression” [Toxicology and Applied Pharmacology, 350 (2018) 78–90] - Guo-Liang Zhang; Jun-Lin Song; Yi Zhou; Rui-Qian Zhang; Shun-Feng Cheng; Xiao-Feng Sun; Guo-Qing Qin; Wei Shen; Lan Li (Toxicology and Applied Pharmacology, 2025)

RASCBEC: Raman spectroscopy calculation via born effective charge - Rui Zhang; Jun Jiang; Alec Mishkin; James N. Fry; Hai-Ping Cheng (Computer Physics Communications, 2025)

Revealing the combined effect of hydroxylamine and hydrazine on nitrogen removal performance of completely autotrophic nitrogen removal over nitrite (CANON) process - Xin Ma; Jia-Min Zhou; Ying-Jun Sun; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Ying Chen; Ren-Cun Jin; Qian-Qian Zhang (Bioresource Technology, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

A new anti-inflammatory thujane monoterpenoid glycoside ester from Pittosporum heterophyllum Franch - Jia-Qi Ding; Sheng-Nan Guan; Yu-Feng Zhang; Zhao-Xuan Wang; Wei-Zhen Kong; Jun-Rui Ren; Xiu-Yun Zhang (Natural Product Research, 2025)

Renewable energy investment under carbon trading mechanism: the impact of green financing and carbon emission quota - Jun Wang; Weicai Peng; Chenhao Ke; Zhongzhi Wang; Shitao Zhang; Zhaobiao Rui; Xiaomeng Shi (Environment, Development and Sustainability, 2025)

Advances in thermochemical valorization of biomass towards carbon neutrality - Jun Zhang; Jing Gu; Rui Shan; Haoran Yuan; Yong Chen (Resources, Conservation and Recycling, 2025)

An effective strategy for high-value utilization of chromite ore processing residue (COPR) through reductive alkali roasting and physical separation - Cheng Tian; Cunfang Lu; Jun Yang; Rui Xu; Min Zhang; Juan Wen; Yelei Wang; Shuo Zhang; Yuanyuan He; Dan Luo; Huazheng Luo; Xingran Zhang (Process Safety and Environmental Protection, 2025)

Inactivation and sublethal injury of Salmonella Typhimurium on beef and in aqueous solution treated with lactic acid - Yunshuang Man; Mengjiao Zhang; Hui Tang; Rui Wen; Rongrong Yang; Lin Mei; Jun Qi; Ruitong Dai; Guoyuan Xiong; Lele Shao (Food Research International, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

Efficient resource recovery from food waste digestate via hydrothermal treatment and its application as organic fertilizer - Hong Chen; Jun Sheng; Qinhui Ye; Jun Li; Xin Yu; Hanyue Wu; Rui Zhang; Shiyi Zhao; Xiaoming Zou; Xiang Li; Gang Xue; Baoling Yuan (Bioresource Technology, 2025)

Roseobacter weihaiensis sp. nov., a cellulose-degrading bacterium isolated from intestinal content of Nipponacmea schrenckii collected from golden beach in Weihai, China - Yu-Rui Li; Ming-Jing Zhang; Yan-Jun Yi; Xiao-Chen Wang; Dong-Mei San; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2025)

Evaluating pulmonary toxicity of PFOS and its alternative OBS using spheroids of A549 cells - Chong-Rui Yao; Yu-Xia Jiang; Si-Ying Li; Zhi-Jie Lu; Xiao-Bing Long; Na Xin; Jin-Ge Zhang; Dong-Dong Ma; Guang-Guo Ying; Wen-Jun Shi (Science of The Total Environment, 2024)

A free radical interlocking co-deposition strategy based on the oxidative pyrolysis mechanism of polyethylene terephthalate to achieve green energy recovery - Weiwen Gu; Tianyi Ma; Xinyu Cui; Xiaoyu Gu; Jun Sun; Jinping Xiong; Rui Wang; Sheng Zhang (Journal of Hazardous Materials, 2024)

The inoculation of Bacillus paralicheniformis and Streptomyces thermoviolaceus enhances the lignocellulose degradation and microbial communities during spent mushroom substrate composting - Jiao Zhang; Ya-Jie Zou; Shun-Li Wang; Wei-Wei Zhang; Qing-Jun Chen; Qiu-Ying Wang; Ti-Kun Guan; Jia-Yan Zhang; Min-Rui Zhao; Guo-Qing Zhang (Environmental Research, 2024)

Vitrification cryo-foil method for shoot tip cryopreservation and virus eradication in apple - Min-Rui Wang; Jun-Hua Bao; Xiao-Yan Ma; Zi-Han Yan; Zhen-Hua Cui; Li-Ying Zhu; Dong Zhang; Qiao-Chun Wang (Cryobiology, 2024)

Multiomics analysis reveal the impact of 17α-Ethinylestradiol on mortality in juvenile zebrafish - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying; Wen-Jun Shi (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Molecular engineering in thizolo[5,4-d]thiazole-based donor-acceptor covalent organic framework Induced high-efficient photosynthesis of H2O2 - Ding-Ming Xue; Yi-Jun Zhang; Jing-Wen Chen; Hao Yang; Rui-Jie Xie; Shi-Chao Qi; Yuan-Qing Bu; Fei Liu; Hou-Hu Zhang; Jacques Lalevée (Chemical Engineering Journal, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Waste lithium-ion batteries for selective transfer hydrogenation of bio-based ethyl levulinate: Experiments, kinetics and economic assessment - Jun Zhang; Zihao Li; Huiyu Liu; Rui Shan; Haoran Yuan; Yong Chen (Chemical Engineering Journal, 2024)

Model test of in-situ remediation for heavy metal-contaminated clayey soil by artificial freezing and shaft washing - Jun Zhang; Wenjun Nie; Mintae Kim; Xianghong He; Dahu Rui; Weidong Pan (Cold Regions Science and Technology, 2024)

Unraveling the effect of electricity price on electric vehicle charging behavior: A case study in Shenzhen, China - Haoxuan Kuang; Xinyu Zhang; Haohao Qu; Linlin You; Rui Zhu; Jun Li (Sustainable Cities and Society, 2024)

Response of soil gross nitrogen mineralization to fertilization practices in China's uplands - Jun Wang; Yinghua Duan; Guanmo Li; Lu Zhang; Dejin Li; Kailou Liu; Xi'an Cui; Boku Zhou; Hongjun Gao; Xiaori Han; Junyong Ma; Shutang Liu; et al. (Journal of Cleaner Production, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Inflammatory microenvironment activation-targeted self-delivery nanomedicine for effective rheumatoid arthritis treatment - Xinrui Dong; Haibao Liu; Rui Sun; Shuwen Tan; Gaoyang Li; Xuerou Jin; Xiaoqin Zhang; Zhiyi Xiao; Dingxiang Li; Jun-Li Cao; Xiaoran Deng (Chemical Engineering Journal, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

In-situ growth of Ni, Co-Prussian blue nanocubes on molten salt etched lamellar Ti3C2Tx/Ni for enhanced hybrid capacitive deionization - Wen Xi; Youfang Zhang; Jianing Hu; Zongchang Li; Rui Wang; Huanwen Wang; Yansheng Gong; Beibei He; Jun Jin (Chemical Engineering Journal, 2024)

Thermal comfort of healthcare facilities in China: A review - Rui Guan; Jun Lu; Zhen Peng; Siyu Ma; Wu Deng; Zhiang Zhang; Paolo Beccarelli; Tong He (Building and Environment, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

Freshwater microconchids from the Tanzhuang Formation (Middle-Late Triassic) in North China - Hao Yang; Yue Su; Hui-Jun Chen; Yi-Ran Cao; Meng-Yang Zhang; Rui Li; Dao-Liang Chu (Palaeoworld, 2024)

Reason and control strategy for denitrification and anammox sludge flotation in nitrogen removal process: Mechanisms, strategies and perspectives - Xin Ma; Xin-Rui Zhang; Ying-Jun Sun; Zhi-Han Xi; Jin-Ze Liu; Ze-Tong Feng; Jia-Min Zhou; Xin-Tao Liu; Ying Wang; Ren-Cun Jin; Qian-Qian Zhang (Environmental Research, 2024)

An efficient Au/ZnO catalyst for the photocatalytic conversion of methane to formaldehyde - Yan-Qun Chen; Lei-Xin Mao; Rui-Xin Zhang; Xin-Yu Zhang; Zhi-Hua Gao; Lei Liu; Wei Huang; Zhi-Jun Zuo (Chemical Engineering Journal, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

Anion vacancy engineering in carbon coating VS4 microspheres assembled by nanorod arrays for high-performance rechargeable Mg-Li hybrid batteries - Xu Zhang; Qinke Tang; Yana Liu; Yunfeng Zhu; Jiguang Zhang; Jun Wang; Rui Shi (Chemical Engineering Journal, 2024)

Molecularly engineered chitosan-derived poly(aprotic/protic ionic liquids) double-network hydrogel electrolytes for flexible supercapacitors and wearable strain sensors - Hailiang Sheng; Rongli Li; Rui Li; Long Li; Shizhao Li; Yunqi Li; Jili Yuan; Jun Huang; Qinqin Xu; Qiang Zheng; Lihua Zhang; Haibo Xie (Chemical Engineering Journal, 2024)

Sesquiterpenes from Tinospora sinensis and their chemotaxonomic significance - Rui Ao; Ming-Hui Li; Zi-Nan Xiao; Xue-Lian Tang; Jun-Sheng Zhang; Hua Zhang (Biochemical Systematics and Ecology, 2024)

Chemical constituents from the aerial parts of Rhododendron thymifolium and its bioactivities against Tribolium castaneum, Lasioderma serricorne, and Ditylenchus destructor - Jun-Yu Liang; Ying-Ying Yang; Rui Feng; Xiao-Han Zhang; Xu-Dong Wang; Jun-Long Wang; Wei-Bao Kong; Ji Zhang (Journal of Plant Diseases and Protection, 2024)

Simultaneous removal of nitrate nitrogen and ammonium nitrogen by partial denitrification coupled with anammox synergy by zero-valent iron - Jia-Min Zhou; Ying-Jun Sun; Zhi-Han Xi; Zu-Gang Liao; Xin Ma; Ze-Tong Feng; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Ying Chen; Ren-Cun Jin; Qian-Qian Zhang (Journal of Cleaner Production, 2024)

Response of comammox Nitrospira clades A and B communities to long-term fertilization and rhizosphere effects and their relative contribution to nitrification in a subtropical paddy field of China - Rui Tao; Wangying Ding; Keyi Zhang; Yanyan Li; Jun Li; Baowei Hu; Guixin Chu (Journal of Environmental Management, 2024)

Zr-decorated hyper-cross-linked polymers for highly selective upgrading of furfural to furfuryl alcohol - Ying Qiu; Huiyu Liu; Rui Shan; Wei Zhao; Junhua Zhang; Jun Zhang; Haoran Yuan (Fuel, 2024)

Environmental pollution of paraben needs attention: A study of methylparaben and butylparaben co-exposure trigger neurobehavioral toxicity in zebrafish - Jing Xiang; Bing-Rui Lv; Ya-jun Shi; Wen-ming Chen; Ji-liang Zhang (Environmental Pollution, 2024)

Development and efficacy evaluation of nanoliposomes targeting CAFs-LCSCs communication for hepatocellular carcinoma treatment - Liang Kong; Yang Yu; Ru Yang; Rui-bo Guo; Lu Zhang; Jia-hua Wang; Yang Liu; Juan Zang; Chen Yang; Hui-yue Yang; Rui-jun Ju; Xue-tao Li (Chemical Engineering Journal, 2024)

Bifunctional halloysite nanotube-based Ripk1 siRNA delivery system rescues cognitive impairment by targeting amyloid β plaques for clearance and reducing necrotic neurons in Alzheimer’s disease mice - Linmei Wu; Shuo Tan; Yizhu Yan; Lianghao Zhu; Zhaoyuan Wu; Zhihong Liu; Qiang Cheng; Qiuhao Qu; Xinyu Li; Qi Zhang; Jiayi Liu; Jun Chang; et al. (Chemical Engineering Journal, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

Shoot and Root Traits are Associated with Varying Soil Phosphorus Supply in Chinese Cabbage - Hou Sai-sai; Pu Zi-tian; Zhang Rui-fang; Zhang Chi; Wang Hong; Wang Xin-xin; Zhao Jian-jun (Journal of Soil Science and Plant Nutrition, 2024)

Metformin improves cognitive dysfunction through SIRT1/NLRP3 pathway–mediated neuroinflammation in db/db mice - Tian Hu; Jun-Wen Wei; Jia-Yi Zheng; Qing-Yi Luo; Xin-Rui Hu; Qun Du; Ye-Feng Cai; Shi-Jie Zhang (Journal of Molecular Medicine, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Heterologous expression and characterization of two delta glutathione S-transferases genes involved in imidacloprid metabolism in Grapholita molesta - Qin-Wei Pang; Wen-Jie He; Ming-Gao Li; Ming Wang; Xue-Yao Zhang; Li-Jun Zhang; Ling-Ling Gao; Rui-Yan Ma; Yan-Qiong Guo; Qin Yu (Chemosphere, 2024)

Improving effect of N-acetylcysteine on growth and intestinal health in juvenile Cyprinus carpio involve the Nrf2/MAPK/NF-κB pathways - Rui Zhu; Deng-Lai Li; Bao-Yuan Zhang; Liang Li; Guo-Jun Shang; Hao-Tong Wang; Zhi-Yong Yang; Xiao-fang Wei; Si-Tong Meng; Si-Ying Liu; Yin-Tao Wang; Li-Fang Wu; et al. (Aquaculture, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

An emerging antibacterial nanovaccine for enhanced chemotherapy by selectively eliminating tumor-colonizing bacteria - Linfu Chen; Zheyu Kang; Jingjing Shen; Rui Zhao; Yu Miao; Lin Zhang; Zixuan Zheng; Zhemin Zhang; Nanhui Liu; Cheng Wang; Huapan Fang; Jun Zhou; et al. (Science Bulletin, 2024)

Quartz trace element geochemistry and internal morphology as proxies for provenance characterization: Results from the Marwar basin, NW India - Jun Zhang; Rui Li; Manoj K. Pandit; Ting-Guang Lan; Qing Xiong; Yuan-Bao Wu; Jun-Hong Zhao; Wei Wang (Precambrian Research, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Pilot-tests of the coal-fired power plant indirect coupling with multi-source organic solid waste incineration technology - Rui Zhang; Jun Cao; Ling Lei; Yufei Cao; Dong Liu (Fuel, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Ile-Pro-Pro attenuates sympathetic activity and hypertension - Jun-Liu Chen; Rui Ge; Xiu-Zhen Li; Yue Zhang; Wen-Yuan Hao; Na Li; Zhi-Qin Xu; Qi Chen; Yue-Hua Li; Guo-Qing Zhu; Xiao Tan (Journal of Physiology and Biochemistry, 2024)

The cooperative interaction of AOB and comammox clade A drives nitrification and N2O emissions in a long-term organic fertilized paddy soil - Keyi Zhang; Wangying Ding; Xiran Zhao; Jun Li; Guixin Chu; Rui Tao (Applied Soil Ecology, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Direct infusion–multiple reaction monitoring cubed (DI–MRM3) enables widely targeted bi-omics of Colla Corii Asini (Chinese name: Ejiao) - Ting Li; Ke Zhang; Rui Liu; Luyao Ren; Xiaoyun Li; Jun Li; Wenjing Liu; Yuelin Song (Food Chemistry, 2024)

Reduction of heavy metals in municipal solid waste incineration fly ash followed by making transparent glass - Hanlin Shen; Bingjie Lou; Bo Liu; Junjie Zhang; Xiaoyan Zhang; Jun Liu; Rui Zhang; Mingcui Chen; Shengen Zhang (Waste Management, 2024)

Farmers' cooperation preference for solar composting chamber —— From farmers’ multi-dimensional heterogeneity perspective - Yajuan Jia; Rui Shi; Xinqi Zhang; Jiapeng Chen; Jun Gao (Journal of Cleaner Production, 2024)

IL-6/STAT3 axis is hijacked by GCRV to facilitate viral replication via suppressing type Ⅰ IFN signaling - Liang Hu; Yang Xu; Qiu-Shi Zhang; Xiao-Ying Chen; Chun Li; Rui Chen; Guo-Li Hou; Zhao Lv; Tiao-Yi Xiao; Jun Zou; Hong-Quan Wang; Jun-Hua Li (Fish & Shellfish Immunology, 2024)

Recent advances of 2D materials in capacitive deionization - Jun Jin; Wen Xi; Zongchang Li; Jianing Hu; Rui Wang; Yansheng Gong; Beibei He; Huanwen Wang; Youfang Zhang (Desalination, 2024)

Cadmium interacts with nitrogen level and nitrogen form to affect the growth of an invasive plant Alternanthera philoxeroides - Dan Li; Xiao-Gai Wang; Jia-Xin Yang; Yu-Fei Hu; Wen-Yue Lyu; Jun-Cai Xin; Rui Zhang; Zhi-Huan Chen; Chao Si (Aquatic Ecology, 2024)

Unveiling of dietary and gut-microbiota derived B vitamins: Metabolism patterns and their synergistic functions in gut-brain homeostasis - Qi Zhan; Rui Wang; Kiran Thakur; Jing-Yu Feng; Yun-Yang Zhu; Jian-Guo Zhang; Zhao-Jun Wei (Critical Reviews in Food Science and Nutrition, 2024)

A newly isolated strain of Bacillus subtilis W2Z exhibited probiotic effects on juvenile red claw crayfish, Cherax quadricarinatus - Ze-Long Zhang; Jia-Jun Li; Si-Wen Xing; Yao-Peng Lu; Pei-Hua Zheng; Jun-Tao Li; Chen-Guang Hao; Jia-Rui Xu; Jian-An Xian; Li-Min Zhang; Xiu-Xia Zhang (Aquaculture, 2024)

Adsorption properties and mechanisms of geopolymers and their composites in different water environments: A comprehensive review - Hangyi Lin; Jun Zhang; Rui Wang; Wensheng Zhang; Jiayuan Ye (Journal of Water Process Engineering, 2024)

Water-saving irrigation and delayed sowing increased the emission intensity of CH4 and N2O in the rice-wheat rotated field under nighttime warming - Yunsheng Lou; Jun Li; Junhong Guo; Defeng Pan; Zhen Zhang; Li Ma; Rui Li; Lixuan Ren (Agriculture, Ecosystems & Environment, 2024)

Brain-Derived Exosomal CircRNAs in Plasma Serve as Diagnostic Biomarkers for Acute Ischemic Stroke - Xinli Jiang; Rui Zhang; Geng Lu; Yu Zhou; Jianfeng Li; Xinrui Jiang; Shuangshuang Gu; Hongwei Liang; Jun Wang (Journal of Neuroimmune Pharmacology, 2024)

DeepWMH: A deep learning tool for accurate white matter hyperintensity segmentation without requiring manual annotations for training - Chenghao Liu; Zhizheng Zhuo; Liying Qu; Ying Jin; Tiantian Hua; Jun Xu; Guirong Tan; Yuna Li; Yunyun Duan; Tingting Wang; Zaiqiang Zhang; Yanling Zhang; et al. (Science Bulletin, 2024)

Generation of tau dephosphorylation-targeting chimeras for the treatment of Alzheimer’s disease and related tauopathies - Jingfen Su; Yue Xiao; Linyu Wei; Huiyang Lei; Fei Sun; Weixia Wang; Jun Yin; Rui Xiong; Shihong Li; Pei Zhang; Ying Zhou; Xiaochuan Wang; et al. (Science Bulletin, 2024)

Screening androgen receptor agonists of fish species using machine learning and molecular model in NORMAN water-relevant list - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Chang-Er Chen; Guang-Guo Ying; Wen-Jun Shi (Journal of Hazardous Materials, 2024)

Calcium decorated Copper@Nitrogen-Doped carbon towards highly selective hydrogenation of biomass derived furfural - Jun Zhang; Yaoxin Xiao; Rui Shan; Haoran Yuan; Yong Chen (Fuel, 2024)

Effects of antimicrobial peptides from dietary Hermetia illucens larvae on the growth, immunity, gene expression, intestinal microbiota and resistance to Aeromonas hydrophila of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yong-Qi Meng; Jia-Jun Li; Xiu-Xia Zhang; Jun-Tao Li; Jia-Rui Xu; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Molten salt etching synthesis of Ti3C2Tx/Ni composites for highly efficient capacitive deionization - Wen Xi; Tianzhuo Guo; Zeren Xie; Youfang Zhang; Rui Wang; Yansheng Gong; Beibei He; Huanwen Wang; Jun Jin (Desalination, 2024)

Triboelectric nanogenerator based on multi-component crosslinked network hydrogel for intelligent human motion sensing - Kang-Rui Zhu; Lin-Xin Wu; Meng-Nan Liu; Chang-Long Li; Wei-Zhi Song; Kong-Qiang Wei; Jun Zhang; Seeram Ramakrishna; Yun-Ze Long (Chemical Engineering Journal, 2024)

Hollow AMn2O4-δ (A = Co, Zn, Ni) nanotube for direct photo-oxidation of methane to C1 and C2 alcohols at atmospheric pressure and room temperature - Jun Duan; Shiying Fan; Xinyong Li; Jing Wang; Chunpeng Bai; Shixuan Yu; Weitong Ling; Rui Tian; Dongke Zhang (Chemical Engineering Journal, 2024)

TRIM5 as a promising diagnostic biomarker of hepatocellular carcinoma: integrated analysis and experimental validation - Huanxiang Liu; Yuhong Tang; Jiahao Zhang; Gefeng Wu; Qing Peng; Chen Chen; Jun Cao; Rui Peng; Bingbing Su; Daoyuan Tu; Guoqing Jiang; Qian Wang; et al. (Functional & Integrative Genomics, 2024)

The Complete Genomic Sequence of Microbial Transglutaminase Producer, Streptomyces mobaraensis DSM40587 - Xi-long Feng; Rui-qi Zhang; Wei-ge Dong; Zhen-xin Wang; Jun-jie Xiao; Jing Wei; Jin-ming Gao; Jianzhao Qi (Biochemical Genetics, 2024)

SAR image classification using deep features and neighborhood heterogeneity confidence refined spatial constraints - Anjun Zhang; Linsheng Huang; Lu Jia; Rui Ruan; Jun Wang (International Journal of Remote Sensing, 2024)

Topological spin-orbit-coupled fermions beyond rotating wave approximation - Han Zhang; Wen-Wei Wang; Chang Qiao; Long Zhang; Ming-Cheng Liang; Rui Wu; Xu-Jie Wang; Xiong-Jun Liu; Xibo Zhang (Science Bulletin, 2024)

One-step strategy for efficient Cr(VI) removal via phytate modified zero-valent iron: Accelerated electron transfer and enhanced coordination effect - Rui Gan; Yuxuan Ye; Ziyi Zhan; Qiuyue Zhang; Yuwei Deng; Yingjie Liu; Haochen Li; Jun Wan; Xuanyuan Pei; Qiang Li; Fei Pan (Journal of Hazardous Materials, 2024)

Succinylated acetyl-CoA carboxylase contributes to aflatoxin biosynthesis, morphology development, and pathogenicity in Aspergillus flavus - Rui Xie; Bei Zhang; Elisabeth Tumukunde; Zhenhong Zhuang; Jun Yuan; Shihua Wang (International Journal of Food Microbiology, 2024)

Experimental study on the dealkalization of red mud using the freeze-thaw and acid washing method - Dahu Rui; Mingpu Li; Mintae Kim; Jun Zhang; Wenjun Nie; Shuren Wang; Guoyu Li; Shengjie Liu (Cold Regions Science and Technology, 2024)

A particle-scale insight into the face stability of shallow EPB shield tunnels in dry cobble-rich soil - Jun Wang; Guojin Lin; Rui Tang; Yan Zhang; Zhigang Yao; Kun Feng; Ning Tian; Ziquan Chen; Chuan He (Tunnelling and Underground Space Technology, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Effects of dietary astaxanthin on growth performance, muscle composition, non-specific immunity, gene expression, and ammonia resistance of juvenile ivory shell (Babylonia areolate) - Teng Li; Pei-Hua Zheng; Xiu-Xia Zhang; Ze-Long Zhang; Jun-Tao Li; Jia-Jun Li; Jia-Rui Xu; Dong-Mei Wang; Jian-An Xian; Hui Guo; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Effects of dietary chitosan oligosaccharide on the growth, intestinal microbiota and immunity of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yan-Lei Cao; Jia-Rui Xu; Xiu-Xia Zhang; Jia-Jun Li; Jun-Tao Li; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Metal-sensitized Au-Bi2O3 nanoheterojunction for immunogenic cell death-boosted sono-immuno cancer therapy - Guobo Chen; Jun Du; Liping Gu; Qian Wang; Qingwen Qi; Xueyu Li; Rui Zhang; Han Yang; Yuqing Miao; Yuhao Li (Chemical Engineering Journal, 2024)

In situ bioprinting of double network anti-digestive xanthan gum derived hydrogel scaffolds for the treatment of enterocutaneous fistulas - Kang Chen; Jinjian Huang; Ze Li; Jinpeng Zhang; Sicheng Li; Canwen Chen; Ye Liu; Guiwen Qu; Yitian Teng; Rui Ma; Zongan Li; Yungang Jiang; et al. (Carbohydrate Polymers, 2024)

The lncRNA20718-miR6022-RLPs module regulates tomato resistance to Phytophthora infestans - Jia-hui Zhang; Hong-bo Wei; Yu-hui Hong; Rui-rui Yang; Jun Meng; Yu-shi Luan (Plant Cell Reports, 2024)

Heavy Metal Scavenger Metallothionein Rescues Against Cold Stress-Evoked Myocardial Contractile Anomalies Through Regulation of Mitophagy - Zhaohui Pei; Yayuan Xiong; Shasha Jiang; Rui Guo; Wei Jin; Jun Tao; Zhenzhong Zhang; Yingmei Zhang; Yunzeng Zou; Yan Gong; Jun Ren (Cardiovascular Toxicology, 2024)

Correction to: Type I methanotrophs dominated methane oxidation and assimilation in rice paddy fields by the consequence of niche differentiation - Shengmeng Zheng; Shaohong Deng; Chong Ma; Yinhang Xia; Hang Qiao; Jun Zhao; Wei Gao; Qiang Tu; Youming Zhang; Yichao Rui; Jinshui Wu; Yirong Su; et al. (Biology and Fertility of Soils, 2024)

Type I methanotrophs dominated methane oxidation and assimilation in rice paddy fields by the consequence of niche differentiation - Shengmeng Zheng; Shaohong Deng; Chong Ma; Yinhang Xia; Hang Qiao; Jun Zhao; Wei Gao; Qiang Tu; Youming Zhang; Yichao Rui; Jinshui Wu; Yirong Su; et al. (Biology and Fertility of Soils, 2024)

Pathways for regions to achieve carbon emission peak: New insights from the four economic growth poles in China - Yu-Jie Hu; Fali Duan; Honglei Wang; Chengjiang Li; Rui Zhang; Bao-Jun Tang (Science of The Total Environment, 2024)

Polysulfide regulation by defect-modulated Ta3N5− electrocatalyst toward superior room-temperature sodium-sulfur batteries - Zhen Zhang; Dan Luo; Jun Chen; Chuyin Ma; Matthew Li; Haoze Zhang; Renfei Feng; Rui Gao; Haozhen Dou; Aiping Yu; Xin Wang; Zhongwei Chen (Science Bulletin, 2024)

Synergizing policies for carbon reduction, energy transition and pollution control: Evidence from Chinese power generation industry - Yu-Jie Hu; Rui Zhang; Honglei Wang; Chengjiang Li; Bao-Jun Tang (Journal of Cleaner Production, 2024)

Co-pyrolysis mechanism of waste vehicle seats derived artificial leather and foam - Jun Zhang; Shengliang Zhong; Chengyu Li; Rui Shan; Haoran Yuan; Yong Chen (Journal of Cleaner Production, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

Carbon monoxide-based immunogenic cell death amplifier remodels the hypoxic microenvironment for tumor sono-immunotherapy - Qian Wang; Zongyan He; Rui Zhang; Jun Du; Lejin Zhu; Xueyu Li; Han Yang; Yuqing Miao; Yuhao Li (Chemical Engineering Journal, 2024)

Sulfite activation of Fe-Mn bimetallic oxides for rapid oxidative removal of As(III) in water: Involvement of active Mn(III) - Guiyuan Cai; Yu Tian; Lipin Li; Wenxuan Zhang; Rui Huang; Jun Zhang; Qinyu Wang; Hua Xu; Yifeng Zhang (Chemical Engineering Journal, 2024)

Comparison of Seed Germination Characteristics Between Cultivated and Wild Barley - Le Xu; Haoran Gao; Jun Wu; Siyu Wang; Rui Pan; Wenying Zhang (Journal of Plant Growth Regulation, 2024)

Effects of nutrients and light in aquatic habitat on the growth of Hydrocotyle vulgaris when expanded from terrestrial to aquatic habitat - Zhi-Huan Chen; Rui Zhang; Jun-Cai Xin; Zi-Han Qian; Shu-Jie Wang; Shang-Yan Qiu; Xue-Ge He; Chao Si (Aquatic Botany, 2024)

Optimal allocation of local climate zones based on heat vulnerability perspective - Rui Zhang; Jun Yang; Xinyue Ma; Xiangming Xiao; Jianhong (Cecilia) Xia (Sustainable Cities and Society, 2023)

Three new flavones from the whole plants of Cassia auriculata Linn. and their antiviral activities - Rui-Feng Xiong; Jun-Na Zheng; Qing-Yang Wu; Ning Jiang; Yuan-Sheng He; Yong-Jun Zhang; Ben-Hui Li; Wei Li; Qiu-Fen Hu; Zhen-Yuan Xia; Yin-Ke Li (Phytochemistry Letters, 2023)

Rare earth regulatory defect engineering: A multifunctional nanoplatform for breast cancer therapy through PANoptosis - Rui Zhang; Guobo Chen; Jun Du; Qian Wang; Qingwen Qi; Xueyu Li; Lejin Zhu; Xingzhou Chen; Baolin Liu; Yuqing Miao; Yuhao Li (Chemical Engineering Journal, 2023)

Remediation of large-scale model experiment for heavy metal contaminated clayey soil: An optimized mass transfer process strategy of freeze-thaw and washing - Dahu Rui; Wenjun Nie; Mintae Kim; Xing Chen; Jun Zhang; Shuren Wang; Yuzuru Ito (Cold Regions Science and Technology, 2023)

Remediation of Pb- and, Cd-contaminated soil through magnetic-modified eluent synergetic freeze-thaw and washing - Yuru Wang; Dahu Rui; Wenjun Nie; Mintae Kim; Daoning Hu; Jun Zhang; Jianfei Liu (Cold Regions Science and Technology, 2023)

Peripheral BDNF Regulates Somatosensory–Sympathetic Coupling in Brachial Plexus Avulsion-Induced Neuropathic Pain - Hang Xian; Huan Guo; Yuan-Ying Liu; Jian-Lei Zhang; Wen-Chao Hu; Ming-Jun Yu; Rui Zhao; Rou-Gang Xie; Hang Zhang; Rui Cong (Neuroscience Bulletin, 2023)

Serum HBV RNA levels among untreated adults with chronic hepatitis B in distinct immune phases and liver histopathology statuses - Qin Xu; Hai Ding; Tao Bai; Rui Huang; Jian Wang; Jun Zhang; Hewei Luan; Jun Wang; Yue Yang; Yuxin Chen (Journal of Molecular Histology, 2023)

Dietary supplementation of pyridoxine can enhance the growth performance and improve the protein, lipid utilization efficiency of mandarin fish (Siniperca chuatsi) - Rui-Peng Xie; Xu-Fang Liang; Di Peng; Qi-Wei Zhang; Dong-Liang Wu; Jun-Liang Chen; Ming Zeng (Fish Physiology and Biochemistry, 2023)

Associations of 10 trace element levels in the whole blood with risk of three types of obesity in the elderly - Rui Zhan; Lin Liu; Maoyuan Yang; Yating Ren; Zhihao Ge; Jun Shi; Ke Zhou; Jiebao Zhang; Hongjuan Cao; Linsheng Yang; Kaiyong Liu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

A chronostratigraphic and biostratigraphic framework for the Yanliao Biota of northeastern China: Implications for Jurassic terrestrial ecosystems and evolution - Yuling Li; Su-Chin Chang; Haichun Zhang; Jun Wang; Rui Pei; Daran Zheng; Yan Fang; Sidney R. Hemming (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Mechanistic insight into the hydrogen transfer pathway for selective upcycling of PET to arenes - Huiyu Liu; Jun Zhang; Jing Gu; Rui Shan; Haoran Yuan; Yong Chen (Journal of Cleaner Production, 2023)

Constituents of the fruits of Rubus chingii Hu and their neuroprotective effects on human neuroblastoma SH-SY5Y cells - Jingyi Wang; Xue Zhang; Jundong Yu; Jun Du; Xiaohong Wu; Liang Chen; Rui Wang; Yingchun Wu; Yiming Li (Food Research International, 2023)

DEM study on evolution of soil arching in a deep trapdoor in seismic shaking conditions - Rui-Xiao Zhang; Dong Su; Hao Xiong; Xing-Tao Lin; Yuan-Jun Jiang; Xiang-Sheng Chen (Computers and Geotechnics, 2023)

Insights into simultaneous adsorption of orthophosphate (PO43−) and 1-hydroxyethane 1,1-diphosphonic acid (HEDP) by kaolin/lanthanum carbonate composites: Experimental analysis and DFT calculations - Jun Wan; Rui Li; Xiaonan Feng; Jiazhi Yang; Yuxuan Ye; Sifeng Jian; Xiaowei Zhang (Chemical Engineering Journal, 2023)

Constructing MoS2-SnS heterostructures on N-doped carbon nanosheets for enhanced catalytic conversion of polysulfides in lithium-sulfur batteries - Junpu Zhang; Wen Xi; Feng Yu; Youfang Zhang; Rui Wang; Yansheng Gong; Beibei He; Huanwen Wang; Jun Jin (Chemical Engineering Journal, 2023)

Anti-inflammatory metabolites from the fruits of Pittosporum elevaticostatum - Jun-Rui Ren; Xin-Zheng Liu; Wei-Zhen Kong; Zhao-Xuan Wang; Jin-Ming Gao; Xiu-Yun Zhang (Phytochemistry Letters, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Leaf senescence, nitrogen remobilization, and productivity of maize in two semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Fei Mo; Aziz Khan; Asfa Batool; Wei Zhang; Jun-Sheng Lu; Ying Zhu; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; et al. (European Journal of Agronomy, 2023)

Epoxy-based high-k composite vitrimer: With low dielectric loss, high breakdown strength and surface electrical damage repairability - Yu-Cheng Zhang; Wen-Dong Li; Xin Zhao; Fan-Bo Meng; Peng Sun; Chao Wang; Guang-Zhi Guo; Wen-Rui Li; Guan-Jun Zhang (Chemical Engineering Journal, 2023)

Astragaloside IV-mediated inhibition of oxidative stress by upregulation of ghrelin in type 2 diabetes–induced cognitive impairment - Rui-hua Zhang; Shan-shan Cao; Yong Shi; Xin Wang; Lei-lei Shi; Yu-han Zhang; Chao-jun Han; Bin Wang; Liang Feng; Ji-ping Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Adjusting effects of pyrolytic volatiles interaction in char to upgrade oil by swelling waste nylon-tire - Rui Huang; Qiangqiang Ren; Jialin Zhang; Limo He; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Song Hu; Jun Xiang (Waste Management, 2023)

Linking soil phosphorus fractions to associated microbial functional profiles under crop rotation on the Loess Plateau of China - Yang Liu; Rui Liu; Rajan Ghimire; Nannan Zhang; Sha Zhou; Fazhu Zhao; Jun Wang (Soil and Tillage Research, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Comprehensive understanding of tetracycline hydrochloride adsorption mechanism onto biochar-based gel pellets based on the combination of characterization-based and approximate site energy distribution methods - Bai-Qin Zhou; Qian-Qian Sang; Yu-Jun Wang; Hui Huang; Fang-Jun Wang; Rui-Chun Yang; Yuan-Tian Zhao; Zi-Jie Xiao; Chun-Yue Zhang; Hui-Ping Li (Journal of Cleaner Production, 2023)

Numeric and nonnumeric information input to predict adsorption amount, capacity and kinetics of tetracyclines by biochar via machine learning - Bai-Qin Zhou; Rui-Chun Yang; Hui-Ping LI; Yu-Jun Wang; Chun-Yue Zhang; Zi-Jie Xiao; Zhong-Qi He; Wei-Hai Pang (Chemical Engineering Journal, 2023)

Investigating the electrochemical performance of MnO2 polymorphs as cathode materials for aqueous proton batteries - Yujie Dai; Jianze Zhang; Xiaorong Yan; Guoqing Zhao; Mingsheng Yang; Jiakui Xiong; Rui Li; Naihua Miao; Haiping Yu; Mingjun Hu; Jingru Liu; Jun Yang (Chemical Engineering Journal, 2023)

Punicalagin relieves lipotoxic injuries on pancreatic β-cells via regulating the oxidative stress and endoplasmic reticulum stress-mediated apoptosis - Ning Wang; Kexin Yang; Jun Wang; Jinghe Liang; Shengbo Yu; Aiqing Zhu; Rui Zhang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Semi-supervised interlayer intelligent recognition method - Shixiang Jiao; Jun Zhao; Yufei He; Shixuan Zhao; Zhenguan Wu; Tianyi Zeng; Rui Zhang (Earth Science Informatics, 2023)

Antibacterial, antiviral, and biodegradable collagen network mask for effective particulate removal and wireless breath monitoring - Peng Zhao; Rui Wang; Jun Xiang; Jinwei Zhang; Xiaodong Wu; Chaojian Chen; Gongyan Liu (Journal of Hazardous Materials, 2023)

Nickel based catalyst supported by carbon aerogel prepared from waste pomelo peel to crack ethanol for hydrogen production: Catalytic performance and mechanism - Jialin Zhang; Song Hu; Yong Ding; Rui Huang; Qiangqiang Ren; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Jun Xiang (Fuel, 2023)

Norethindrone suppress the germ cell development via androgen receptor resulting in male bias - Xiao-Bing Long; Wen-Jun Shi; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying (Aquatic Toxicology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

The first homosporous lycophyte genome revealed the association between the recent dynamic accumulation of LTR-RTs and genome size variation - Ji-Gao Yu; Jun-Yong Tang; Ran Wei; Mei-Fang Lan; Rui-Chen Xiang; Xian-Chun Zhang; Qiao-Ping Xiang (Plant Molecular Biology, 2023)

Pathogenicity characteristics of the entomopathogenic fungus Cordyceps javanica IJ-tg19 to Acyrthosiphon pisum - Di Wang; Pei-Xiang Xing; Hong-Liang Diao; Wen-Wen Zhou; Xian-Wei Li; Li-Jun Zhang; Rui-Yan Ma (BioControl, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Maternal 25(OH)D attenuates the relationship between ambient air pollution during pregnancy and fetal hyperinsulinism - Peng Wang; Wan-jun Yin; Ying Zhang; Xiao-min Jiang; Xiao-guang Yin; Yu-bo Ma; Fang-biao Tao; Rui-xue Tao; Peng Zhu (Chemosphere, 2023)

Mixed scaling deconstruction in vacuum membrane distillation for desulfurization wastewater treatment by a cascade strategy - Libing Zheng; Chenlu Li; Chun Zhang; Sai Kang; Rui Gao; Jun Wang; Yuansong Wei (Water Research, 2023)

A novel fluidized-bed-electrode solid-oxide-fuel-cell reactor for N2O catalytic decomposition - Dongxu Cui; Shiliang Wu; Tao Li; Yuxin Zhang; Sang Jun Yoon; Youn-Sang Bae; Bugae Park; Yinlong Wu; Rui Xiao (Chemical Engineering Journal, 2023)

Local eutectic combined with surface functional treatment: An efficient strategy to lower desorption temperature of bulk magnesium-based hydride - Rui Shi; Haoxing Yan; Jiguang Zhang; Yunfeng Zhu; Yana Liu; Jun Wang; Xiaohui Hu; Liquan Li (Chemical Engineering Journal, 2023)

A new model system for cotton indoor genetic and genomic research - Jun Zhang; Zhanfeng Si; Rui Chen; Wangshu Liu; Yue Shi; Zhuolin Shi; Huan Mei; Yan Hu; Lei Fang; Tianzhen Zhang (Science China Life Sciences, 2023)

The distribution and emission of CO2, CH4 and light hydrocarbons in an anticyclonic eddy of the Kuroshio extension - Xiao-Jun Li; Jian Wang; Hao Qiao; Rui-Chen Zhu; Hong-Hai Zhang; Zhao-Hui Chen; Andrew Montgomery; Shan Zheng; Guang-Chao Zhuang (Frontiers in Marine Science, 2023)
Mesoscale eddies are energetic and swirling circulations that frequently occur in the open ocean. The effects of mesoscale eddies on the biogeochemical cycling of climate-relevant gases remain poorly constrained. We investigated the distribution and air-sea fluxes of CO 2 , methane, and five non–methane hydrocarbons (NMHCs) in an anticyclone eddy of Kuroshio Extension during September 2019. Within eddy core, intense stratification hindered the replenishment of nutrients and favored the growth of small-size phytoplankton, such as Prochlorococcus . Seawater pCO 2 decreased from 406.1 μatm at the eddy outside to 377.5 μatm at the eddy core, accompanied by a decrease in surface seawater temperature from 26.7 °C to 25.2 °C. The vertical distribution of methane (0.3-9.9 nmol L -1 ) was influenced by the eddy process, with a maximum at 80 m in the eddy core, which might be attributed to the degradation of phosphonates sustained by Prochlorococcus . The concentrations of five NMHCs (ethane, ethylene, propane, propylene, and isoprene) ranged from 17.2-126.2, 36.7-168.1, 7.5-29.2, 22.6-64.1, 54.5-172.1, 3.5-27.9 pmol L -1 , respectively. Isoprene correlated well with Chl- a concentrations at the eddy core, while no significant correlation was observed at the eddy outside. Air-sea fluxes of CO 2 and isoprene associated with the eddy core were higher than those of the eddy outside, while the maximum ventilation of methane and other NMHCs (ethane, ethylene, propane, and propylene) was found at the eddy outside. Collectively, physical processes such as eddies impact the production and distribution of light hydrocarbons in seawater and further influence their regional emissions to the atmosphere.

Diversified land conversion deepens understanding of impacts of rapid rubber plantation expansion on plant diversity in the tropics - Bangqian Chen; Jun Ma; Chuan Yang; Xiangming Xiao; Weili Kou; Zhixiang Wu; Ting Yun; Zar Ni Zaw; Piyada Nawan; Ratchada Sengprakhon; Jiannan Zhou; Jikun Wang; et al. (Science of The Total Environment, 2023)

Photo-assisted thermal catalysis for methanol synthesis from methane oxidation on Cu-MOR/g-C3N4 - Yan-Qun Chen; Rui-Xin Zhang; Miao Ren; Ya-Xin Jin; Wen-Jing Wang; Jia-Yao Feng; Zhi-Hua Gao; Zhi-Feng Yan; Yi-Ming Liu; Wei Huang; Lei Liu; Zhi-Jun Zuo (Fuel, 2023)

Anti-hardening effect and mechanism of silkworm sericin peptide in high protein nutrition bars during early storage - Hongtao Zhu; Xiu-Xiu Zhang; Rui Zhang; Jing-Yu Feng; Kiran Thakur; Jian-Guo Zhang; Zhao-Jun Wei (Food Chemistry, 2023)

A sulfonate-functionalized covalent organic framework for record-high adsorption and effective separation of organic dyes - Rui Li; Xihao Tang; Jialin Wu; Kai Zhang; Qianni Zhang; Jiaqi Wang; Jiayue Zheng; Shengrun Zheng; Jun Fan; Weiguang Zhang; Xinle Li; Songliang Cai (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A20 ameliorates disc degeneration by suppressing mTOR/BNIP3 axis-mediated mitophagy - Xin Peng; Cong Zhang; Jia-Wei Gao; Feng Wang; Jun-Ping Bao; Zhi-Min Zhou; Rui Sun; Hang-Yu Ji; Cabral VLF; Xiao-Tao Wu (Genes & Genomics, 2023)

Highly reactive coke made from Low-rank Coal: Relationship between thermal properties and multilevel structure - Xin Zhang; Jun Zhang; Rui Guo; Qiang Xiao; Yawei Feng; Huan Cheng (Fuel, 2023)

Modulation of the interfacial properties of TiN coatings to generate Rigid-Flexible SEI for better SiO anodes - Hebang Shi; He Zhang; Rui Wang; Ming Liu; Zihan Shen; Jingbo Chen; Binbin Wu; Maoqiao Xiang; Jun Li; Huigang Zhang; Pengpeng Lv; Qingshan Zhu (Chemical Engineering Journal, 2023)

Quantify the effect of manure fertilizer addition and optimal nitrogen input on rainfed wheat yield and nitrogen requirement using nitrogen nutrition index - Pengzhao Liu; Xingyu Guo; Dong Zhou; Qi Zhang; Xiaolong Ren; Rui Wang; Xiaoli Wang; Xiaoli Chen; Jun Li (Agriculture, Ecosystems & Environment, 2023)

Flow regime changes in the Lancang River, revealed by integrated modeling with multiple Earth observation datasets - Xingxing Zhang; Liguang Jiang; Zhaofei Liu; Cecile M.M. Kittel; Zhijun Yao; Daniel Druce; Rui Wang; Christian Tøttrup; Jun Liu; Hou Jiang; Peter Bauer-Gottwein (Science of The Total Environment, 2023)

Experimental study on the ultimate bearing capacity of damaged RC arches strengthened with ultra-high performance concrete - Jun Yang; Rui Chen; Zhongya Zhang; Yang Zou; Jianting Zhou; Junrun Xia (Engineering Structures, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Projecting multi-attribute flood regime changes for the Yangtze River basin - Chen Zhang; Fengyun Sun; Sanjib Sharma; Peng Zeng; Alfonso Mejia; Yongpeng Lyu; Jun Gao; Rui Zhou; Yue Che (Journal of Hydrology, 2023)

Long-term effects of optimized fertilization, tillage and crop rotation on soil fertility, crop yield and economic profit on the Loess Plateau - Haoyu Li; Yuanhong Zhang; Yuanguang Sun; Pengzhao Liu; Qi Zhang; Xiaoli Wang; Rui Wang; Jun Li (European Journal of Agronomy, 2023)

Antibiotics and antibiotic-resistant genes in municipal solid waste landfills: Current situation and perspective - Liyan Song; Shu Yang; Zhourui Gong; Jun Wang; Xianyang Shi; Yangqing Wang; Rui Zhang; Yongchun Wu; Yongli Z. Wager (Current Opinion in Environmental Science & Health, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Kinetic study for thermocatalytic degradation of waste mixed cloth over antibiotic residue derived carbon-based solid acids - Chengyu Li; Jun Zhang; Rui Shan; Haoran Yuan; Yong Chen (Fuel, 2023)

New insights into the regulation mechanism of red claw crayfish (Cherax quadricarinatus) hepatopancreas under air exposure using transcriptome analysis - Yao-Peng Lu; Pei-Hua Zheng; Xiu-Xia Zhang; Jun-Tao Li; Ze-Long Zhang; Jia-Rui Xu; Yong-Qi Meng; Jia-Jun Li; Jian-An Xian; An-Li Wang (Fish & Shellfish Immunology, 2023)

Breast adipose metabolites mediates the association of tetrabromobisphenol a with breast cancer: A case-control study in Chinese population - Ai Zhang; Rui Wang; Qianfeng Liu; Zhengjun Yang; Xiaohui Lin; Jing Pang; Xiaoyu Li; Dan Wang; Jiayu He; Jianping Li; Mingyue Zhang; Yue Yu; et al. (Environmental Pollution, 2023)

Insights into the practicability of electrochemical enhanced heterogeneous activation of peroxymonosulfate for the treatment of liquid waste during penicillin g production - Lili Liu; Jun Wang; Jianan Li; Meng Zhang; Yunxiao Zhang; Rui Zhan; Jiaxin Li; Zhiping Wang (Chemical Engineering Journal, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

Spatial distribution and quantitative source identification of nutrients and beneficial elements in the soil of a typical suburban area, Beijing - Qin-Rui Zhang; Sheng-Qiang Zhang; Yong Huang; Huan Li; Yan-Hui Jia; Jun Li; Guo-Li Yuan (Environmental Monitoring and Assessment, 2023)

Effects of Dietary Eucommia ulmoides Leaf Extract on Growth, Muscle Composition, Hepatopancreas Histology, Immune Responses and Microcystin-LR Resistance of Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Yao-Peng Lu; Pei-Hua Zheng; Jia-Rui Xu; Yan-Lei Cao; Jun-Tao Li; Chen-Guang Hao; Ze-Long Zhang; Jian-An Xian; Xiu-Xia Zhang; An-Li Wang (Fishes, 2022)
The objective of the present study was to investigate the effects of different doses of dietary Eucommia ulmoides leaf extract (ELE) on juvenile red claw crayfish (Cherax quadricarinatus). A total number of 720 red claw crayfish (initial body weight of 0.24 ± 0.01 g) were randomly assigned to six groups and fed diets containing 0 (Diet 1), 0.5 (Diet 2), 1 (Diet 3), 2 (Diet 4), 4 (Diet 5) and 10 (Diet 6) g dry weight (dw) ELE kg (dw)−1 diets for eight weeks and challenged with microcystin-LR stress. The results indicated that dietary supplementation with 1–2 g dw ELE kg (dw)−1 diet could significantly improve the weight gain rate (WGR) and specific growth rate (SGR) of crayfish. Muscle crude protein contents of crayfish fed Diet 2, Diet 3, and Diet 4 were significantly higher than those of the control group. Compared with the control group, dietary ELE could increase total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GPx), acid phosphatase (ACP), alkaline phosphatase (AKP), and phenoloxidase (PO) activities and decrease malondialdehyde (MDA) level of crayfish. Dietary ELE significantly increased the relative expression levels of SOD, thioredoxin 1 (TRX1), GPx, selenium-dependent glutathione peroxidase (Se-GPx), cytochrome P450 (CYP450), anti-lipopolysaccharide factor (ALF) and C-type lysozyme (C-LZM) mRNA of crayfish compared with the control group during the feeding experiment. When subjected to MC-LR stress for 48 h, the mRNA expression levels of SOD, GPx, Se-GPx, glutathione-s-transferase 1 (GST1), ALF, hemocyanin (HEM), and C-LZM in the hepatopancreas could be improved to varying degrees compared with the Diet 1. Supplementation of 1–2 g dw ELE kg (dw)−1 diet could improve the survival rate (SR) of crayfish under MC-LR stress. These results indicated that dietary ELE (1–2 g dw ELE kg (dw)−1 diet) could improve the growth performance, muscle protein, and non-specific immune response and increase the SR of crayfish under MC-LR stress by regulating the mRNA expression levels of the immune- and antioxidant-related genes.

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

Enhancing extracellular electron transfer through selective enrichment of Geobacter with Fe@CN-modified carbon-based anode in microbial fuel cells - Xiao-Long Cheng; Qiang Xu; Qian-Wen Yang; Rui-Rui Tian; Biao Li; Su Yan; Xue-Ying Zhang; Jun Zhou; Xiao-Yu Yong (Environmental Science and Pollution Research, 2022)

Typhoon-Resistant Performance Assessment of Coastal Rural Residential Keel Brick Walls Reinforced with High Ductility Concrete - Qiang Li; Jun Zhang; Rui Wang; Jing Liu; Ping Li (Journal of Marine Science and Engineering, 2022)
The keel brick wall belongs to the rural residential exterior wall unique to the southeast coastal region of China. The wooden keel inside the wall and the external tie members can improve the stability of the whole wall. However, due to the age of construction, the wooden keel inside the existing residential keel brick walls has basically rotted and lost the tie with the external members, which seriously reduces the stability of the whole wall. Moreover, the collapse of keel brick walls caused by typhoons has become more and more frequent in recent years, seriously endangering the lives and properties of residents. Therefore, it is necessary to carry out reinforcement and repair for the existing residential buildings with keel brick walls. In this paper, the keel brick walls of rural houses in Ningbo area were taken as the research object, a framework for evaluating the performance of keel brick walls against typhoons was established, tests on the lateral force resistance of keel brick walls reinforced with high ductility concrete and mortar were carried out. With the help of typhoon full-track simulation and wind field simulation technology, the 600-year near-surface typhoon wind speeds affecting Ningbo area were obtained. A joint probability distribution model of multi-directional extreme wind speed was constructed using t-Copula function to determine the mixed wind climate of Ningbo area. The extreme wind loads that keel brick walls can withstand under four types of reinforcement were finally given. The results show that the high ductility concrete reinforcement has great advantages over mortar reinforcement and avoids brittle damage of the masonry structure. The keel brick walls reinforced with single-sided mortar can withstand wind loads of a 3-year return period, the keel brick walls reinforced with single-sided high ductile concrete can withstand extreme wind loads of a 110-year return period, while the keel brick walls reinforced with double-sided mortar as well as double-sided high ductile concrete can withstand extreme wind loads of well over a 110-year return period.

Birth-site habitat selection of wild alpine musk deer (Moschus chrysogaster) in the northeastern qing-tibetan plateau of China - Liquan Shen; Haoxiang Gao; Jiayi Wu; Gong Wang; Rui Liu; Jun Qi; Xueyan Zhang; Aiping Zhang; Lei Chen; Yizhen Zhang; Chunling Wang; Dongming Qi; et al. (Biologia, 2022)

Modification of alternative splicing in bovine somatic cell nuclear transfer embryos using engineered CRISPR-Cas13d - Rui Cheng; Xiaoman Zheng; Yingmei Wang; Xing Ma; Xin Liu; Wenjun Xu; Mengyun Wang; Yuanpeng Gao; Xupeng Xing; Chuan Zhou; Hongzheng Sun; Zekun Guo; et al. (Science China Life Sciences, 2022)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Loss of Myomixer Results in Defective Myoblast Fusion, Impaired Muscle Growth, and Severe Myopathy in Zebrafish - Ping Wu; Pengzheng Yong; Zhanxiong Zhang; Rui Xu; Renjie Shang; Jun Shi; Jianshe Zhang; Pengpeng Bi; Elizabeth Chen; Shaojun Du (Marine Biotechnology, 2022)

Combined Effects of Eco-Substrate and Carbon Addition on Water Quality, Fish Performance and Nutrient Budgets in the Pond Polyculture System - Kun Guo; Zhigang Zhao; Jun Xie; Liang Luo; Shihui Wang; Rui Zhang; Wei Xu; Xiaoli Huang (Fishes, 2022)
Traditional aquaculture can cause serious environmental pollution. Biofilm and biofloc technology have the potential to limit aquaculture pollution. An outdoor experiment was conducted to evaluate the combined effects of eco-substrates and carbon addition on water quality, fish performance and nutrient budgets in the pond polyculture system. In the treatment group, the total ammonia nitrogen, nitrate nitrogen, nitrite nitrogen, and total nitrogen of the water were significantly lower compared to the control group (p 92%) and P (>95%) input during the experiment. Comprehensive accumulation was the main N (>58%) and P (>69%) output. The N and P feed input and comprehensive accumulation output declined in the treatment group. The N utilization efficiency in the experimental group increased slightly (p > 0.05), while the P utilization efficiency in the experimental group was significantly higher compared to the control (p

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

The effects of dietary fermented wheat bran polysaccharides on mucosal and serum immune parameters, hepatopancreas antioxidant indicators, and immune-related gene expression of common carp (Cyprinus carpio) juveniles - Rui-Fang Wang; Yuan Wang; Jun Zhang; Mei-Qi Weng; Yu-Hui Liu; Qiu-Yan Cheng; Min Song; Yan-Ping Yang; Xiao-Ping An; Jing-Wei Qi (Aquaculture International, 2022)

Hydrochemical Evolution and Nitrogen Behaviors in Coastal Groundwater Suffered From Seawater Intrusion and Anthropogenic Inputs - Yu Dun; Junhong Ling; Rui Wang; Jun Wei; Qianyi Zhou; Yingjie Cao; Yizhang Zhang; Yingxue Xuan (Frontiers in Marine Science, 2022)
Coastal aquifers play key roles in providing freshwater resources to maintain the social and economic development in coastal areas. However, climate change and human activities have dramatically affected the quantities and qualities of groundwater in coastal aquifers. In this study, stoichiometric analysis of hydrogeochemistry, multivariate analysis, and isotopic trancing techniques were used to reveal the local hydrochemistry characteristics, the natural and anthropogenic origins, and the major hydrochemical evolution in a typical coastal aquifer located in the Pearl River estuary. According to hydrogeological conditions and groundwater burial conditions, the aquifer was divided into three zones, namely, semiconfined fissure groundwater (SFGW), recharged fissure groundwater (RFGW), and porous medium groundwater (PGW). Seawater intrusion, ion exchange, water–rock reaction, and human activities were the main controlling factors affecting the characteristics of groundwater, but there were significant differences in the main controlling effects of different zones. Among them, the samples from the SFGW was severely affected by seawater intrusion, and the contributions of seawater ranged from 6% to 97%. Obvious cation exchange process occurred during the seawater intrusion. The hydrochemical characteristics of the PGW and the RFGW were mainly controlled by water–rock interaction. In addition, human activities had further influence on the hydrochemical characteristics of groundwater, which resulted in elevated nitrate–nitrogen (NO 3 − –N). The mean NO 3 –N concentrations in the PGW and the SFGW were 6.58 and 3.07 mg/L, respectively. Furthermore, the δ 15 N–NO 3 − and δ 18 O–NO 3 − values in these two regions ranged from +2.35‰ to +27.54‰ and from +0.39‰ to +18.95‰, respectively, indicating that the anthropogenic input contributed to the increased nitrate. Redox analysis and dual nitrogen isotopic evidence indicated that denitrification was the predominant biogeochemical process in the PGW and the RFGW. This study highlights the impacts of seawater intrusion and anthropogenic inputs on hydrochemical evolution and nitrogen behaviors in coastal groundwater, which provides a scientific basis for the management of groundwater resources in coastal aquifers.

Roseicella aquatilis sp. nov., isolated from freshwater lake - Dan-Dan Zhang; Ya-Nan Zhao; Rui-Han He; Yu-Qi Yan; Zong-Jun Du (Archives of Microbiology, 2022)

Failure mechanisms and risk mitigation of check dams on the Chinese Loess Plateau: A case study at the Gutun Gully - Rui-jun Jiang; Mao-sheng Zhang; Li Feng; Ping-ping Sun (Journal of Mountain Science, 2022)

In vitro Scolicidal Efficacy of 5-Fluorouracil and Radiation Against Protoscoleces of Echinococcus granulosus Sensu Lato - Pengfei Lu; Jun Li; Rui Mao; Hongzhi Qi; Liping Yang; Qin Zhou; Mengxiao Tian; Wenbao Zhang; Yongxing Bao (Acta Parasitologica, 2022)

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

Mechanism of Adipose-Derived Mesenchymal Stem Cell-Derived Extracellular Vesicles Carrying miR-21-5p in Hyperoxia-Induced Lung Injury - Yunfei Wu; Zhihui Zhang; Jun Li; Hai Zhong; Rui Yuan; Zihui Deng; Xu Wu (Stem Cell Reviews and Reports, 2022)

Correction to: A native Trichoderma harzianum strain Th62 displays antagonistic activities against phytopathogenic fungi and promotes the growth of Celosia cristata - Xue-Yue Hou; Yue-Feng Wang; Chuan-Ying Jiang; Tong-Tong Zhai; Rui Miao; Jun-Jie Deng; Zhi-Hong Yao; Rong-Shu Zhang (Horticulture, Environment, and Biotechnology, 2022)

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

Two new threonine-containing metabolites from fungus Curvularia inaequalis strain HS-FG-257 - Shao-Yong Zhang; Jian-Song Li; Hui Zhang; Huan Qi; Rui-Jun Wang; Chou-Fei Wu; Li-Qin Zhang; An-Liang Chen; Ji-Dong Wang; Zhi-Kui Hao (Natural Product Research, 2022)

A dice similarity measure for TBM penetrability classification in hard rock condition with the intuitionistic fuzzy information of rock mass properties - Rui Yong; Jun Ye; Shi-Gui Du; He Zhang; Leiyu Gu; Hang Lin (European Journal of Environmental and Civil Engineering, 2021)

Evaluation of the Crack Propagation Capacity of Hard Rock Based on Stress-Induced Deformation Anisotropy and the Propagation Angle of Volumetric Strain - Qiang Han; Xia-Ting Feng; Chengxiang Yang; Rui Kong; Jun Zhao; Yan Zhang (Rock Mechanics and Rock Engineering, 2021)

Numerical simulation study on the seepage characteristics of coal seam infusion effected by mining-induced stress - Yanbin Yu; Qilin Xin; Weimin Cheng; Jun Rui; Xin Zhang (Bulletin of Engineering Geology and the Environment, 2021)

Loganin ameliorates depression-like behaviors of mice via modulation of serotoninergic system - Chen-Hao Pan; Cong-Yuan Xia; Yu Yan; Yan Han; Rui Shi; Jun He; Ze-Xing Wang; Yu-Ming Wang; Wei-Ku Zhang; Jie-Kun Xu (Psychopharmacology, 2021)

Circular RNA circ-CHI3L1.2 modulates cisplatin resistance of osteosarcoma cells via the miR-340-5p/LPAATβ axis - Zehua Zhang; Qiang Zhou; Fei Luo; Rui Zhou; Jianzhong Xu; Jun Xiao; Fei Dai; Lei Song (Human Cell, 2021)

Oxiracetam Mediates Neuroprotection Through the Regulation of Microglia Under Hypoxia-Ischemia Neonatal Brain Injury in Mice - Dan Wang; Yanbang Wei; Jingxia Tian; Dong He; Rui Zhang; Xiaoshuai Ji; Xiaoming Huang; Jun Sun; Jiajia Gao; Zixiao Wang; Qi Pang; Qian Liu (Molecular Neurobiology, 2021)

Estimation of the vertically integrated leaf nitrogen content in maize using canopy hyperspectral red edge parameters - Pengfei Wen; Zujiao Shi; Ao Li; Fang Ning; Yuanhong Zhang; Rui Wang; Jun Li (Precision Agriculture, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Research on fault recognition method combining 3D Res-UNet and knowledge distillation - Jing Wang; Jun-Hua Zhang; Jia-Liang Zhang; Feng-Ming Lu; Rui-Gang Meng; Zuoqian Wang (Applied Geophysics, 2021)

Paenibacillus puerhi sp. nov., isolated from the rhizosphere soil of Pu-erh tea plants (Camellia sinensis var. assamica) - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Xing-Hua Wang; Wen-Jie Zhang; Li Zhuang; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

Experimental validation of a new semi-empirical impact force model of the dry granular flow impact against a rigid barrier - Yuan-Jun Jiang; Xiao-Yi Fan; Li-Jun Su; Si-you Xiao; Jing Sui; Rui-Xiao Zhang; Yue Song; Zhi-Wen Shen (Landslides, 2021)

A native Trichoderma harzianum strain Th62 displays antagonistic activities against phytopathogenic fungi and promotes the growth of Celosia cristata - Xue-Yue Hou; Yue-Feng Wang; Chuan-Ying Jiang; Tong-Tong Zhai; Rui Miao; Jun-Jie Deng; Zhi-Hong Yao; Rong-Shu Zhang (Horticulture, Environment, and Biotechnology, 2021)

Selective regulation in ribosome biogenesis and protein production for efficient viral translation - Hui-Jun Dong; Rui Zhang; Yu Kuang; Xiao-Jia Wang (Archives of Microbiology, 2021)

A study on the reservoir controlling characteristics and mechanism of the strike slip faults in the northern slope of Tazhong uplift, Tarim Basin, China - Zhongpei Zhang; Yuan Kang; Huixi Lin; Jun Han; Rui Zhao; Xiuxiang Zhu; Zhixing Ru; Chongyang Xiao (Arabian Journal of Geosciences, 2021)

New potential strains for controlling Spodoptera frugiperda in China: Cordyceps cateniannulata and Metarhizium rileyi - Ye-Ming Zhou; Wen Xie; Jia-Qin Ye; Tao Zhang; Ding-Yin Li; Jun-Rui Zhi; Xiao Zou (BioControl, 2020)

Utilizing borehole electrical image and conventional logs to characterize petrology of mixed volcanic and sedimentary rocks in Jiamuhe Formation at JL2 Wellfield, Zhongguai Uplift, Junggar Basin, NW China - Rui Yuan; Lei Zhang; Qinghai Xu; Youlun Feng; Zhiyuan An; Jun Wu; Kang Zhao; Shuai Liu; Peng Huang (Arabian Journal of Geosciences, 2020)

Prevalence of Clonorchis sinensis infection in fish in South‐East Asia: A systematic review and meta‐analysis - Ying Zhang; Qing‐Long Gong; Qing‐Bo Lv; Yang‐Yuan Qiu; Yan‐Chun Wang; Hong‐Yu Qiu; Xin‐Rui Guo; Jun‐Feng Gao; Qiao‐Cheng Chang; Chun‐Ren Wang (Journal of Fish Diseases, 2020)
Clonorchis sinensis , an important fish‐borne zoonotic trematode, is widely distributed in South‐East Asia, especially in China. Infections from human and animal reservoir hosts occur due to the consumption of raw or undercooked fish with C. sinensis metacercariae. This study aimed to evaluate the prevalence of C. sinensis metacercariae in fish in South‐East Asia via systematic review and meta‐analysis. We searched PubMed, ScienceDirect, China National Knowledge Infrastructure, Wanfang and Chongqing VIP databases for studies published between 1976 and 2020 that are related to the prevalence of C. sinensis metacercariae in fish. Studies were screened with keywords based on inclusion and exclusion criteria. Seventy‐one eligible articles were identified, covering three countries: China, Korea and Vietnam. The pooled prevalence of C. sinensis metacercariae in fish from South‐East Asia was 30.5%, with 35.1% in China, 29.7% in Korea and 8.4% in Vietnam. In subgroup analyses of climate, season, water source and publication date, the highest prevalence was identified in the Dwb climate type (43.3%), summer (70.2%), river (34.5%) and pre‐2001 publications (38.9%), respectively. In comparison, the lowest prevalence was found in the Dfa climate type (14.5%), winter (19.5%), lake (8.0%) and post‐2001 publications (23.8%). Meta‐regression results indicated that country ( p = .009), the published time ( p = .035) and water source subgroups ( p = .003) may be the source of heterogeneity. Overall, our study indicates that a high prevalence of C. sinensis infections occurs in fish in China, Korea and Vietnam, illuminating a significant public health concern in these countries.

Psychroflexus maritimus sp. nov., isolated from coastal sediment - Yan-Lin Zhong; Rui Zhang; Xiao-Yu Zhang; Li-Xue Yu; Meng-Fan Zhao; Zong-Jun Du (Archives of Microbiology, 2020)

Surface fractal dimensions as a characterization parameter for methane adsorption–induced coal strains - Jie Zhu; Yang Zhang; Rui Zhang; Bo Zhang; Jun Tang; Fa He (Arabian Journal of Geosciences, 2020)

Low-frequency swell noise suppression based on U-Net - Rui-qi Zhang; Peng Song; Bao-hua Liu; Xiao-bo Zhang; Jun Tan; Zhi-hui Zou; Chuang Xie; Shao-wen Wang (Applied Geophysics, 2020)

Molecular Characterization and Promoter Analysis of Novel Sugar Transporter Gene ScERD6 in Sugarcane - Xiao-Rong Miao; Xu-Peng Zeng; Jun-Qi Niu; Aamir Mahmood; Li-Tao Yang; Bao-Qing Zhang; Yang-Rui Li (Sugar Tech, 2020)

Seonamhaeicola sediminis sp. nov., isolated from marine sediment - Xiao-Yu Zhang; Rui Zhang; Yan-Lin Zhong; Dai-Wei Xianyu; Zong-Jun Du (Archives of Microbiology, 2020)

The enhancement of NH3-SCR performance for CeO2 catalyst by CO pretreatment - Ping Zhang; Rui-tang Guo; Li-jun Wu; Wei-guo Pan (Environmental Science and Pollution Research, 2020)

The impact of rapid urban expansion on coastal mangroves: a case study in Guangdong Province, China - Bin Ai; Chunlei Ma; Jun Zhao; Rui Zhang (Frontiers of Earth Science, 2020)

Correction to: Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Evaluation on activation energy of deposited clay based on thermo-gravimetric analysis (TGA) and four kinetics models - Rui-xin Yan; Jian-bing Peng; Yan-jun Shen; Yu-liang Zhang; Lin-jun Gu; Shao-kai Wang (Bulletin of Engineering Geology and the Environment, 2020)

CD271 promotes STZ-induced diabetic wound healing and regulates epidermal stem cell survival in the presence of the pTrkA receptor - Min Zhang; Rui Zhang; Xiaohong Li; Yongqian Cao; Kaifeng Huang; Jun Ding; Mengyao Liu; Zhang Feng; Siyuan Yin; Jiaxu Ma; Huayu Zhang; Yibing Wang (Cell and Tissue Research, 2020)

Thermus caldilimi sp. nov., a thermophilic bacterium isolated from a geothermal area - Meng-Meng Li; Wen-Dong Xian; Xiao-Tong Zhang; Yi-Rui Yin; En-Min Zhou; Yi-Ping Ding; Lan Liu; Bao-Zhu Fang; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Structural characterization and immunosuppressive activity of a new pregnane glycoside from Epigynum cochinchinensis - Yu-Ting Shao; Yan Zhao; Hong Zhang; Meng-Jun Jiang; Afsar Khan; Sheng-Bao Cai; Tian-Rui Zhao; Gui-Guang Cheng; Jian-Xin Cao (Natural Product Research, 2019)

Decreased miR-325-5p Contributes to Visceral Hypersensitivity Through Post-transcriptional Upregulation of CCL2 in Rat Dorsal Root Ganglia - Rui Wu; Ping-An Zhang; Xuelian Liu; Yuan Zhou; Meijie Xu; Xinghong Jiang; Jun Yan; Guang-Yin Xu (Neuroscience Bulletin, 2019)

QTL mapping and genetic effect of chromosome segment substitution lines with excellent fiber quality from Gossypium hirsutum × Gossypium barbadense - Shao-qi Li; Ai-ying Liu; Ling-lei Kong; Ju-wu Gong; Jun-wen Li; Wan-kui Gong; Quan-wei Lu; Peng-tao Li; Qun Ge; Hai-hong Shang; Xiang-hui Xiao; Rui-xian Liu; et al. (Molecular Genetics and Genomics, 2019)

The faster-onset antidepressant effects of hypidone hydrochloride (YL-0919) - Li-jun Sun; Li-ming Zhang; Dan Liu; Rui Xue; Yan-qin Liu; Lei Li; Ying Guo; Chao Shang; Jun-qi Yao; You-zhi Zhang; Yun-feng Li (Metabolic Brain Disease, 2019)

ATP induces caspase-3/gasdermin E-mediated pyroptosis in NLRP3 pathway-blocked murine macrophages - Chen-Ying Zeng; Chen-Guang Li; Jun-Xiang Shu; Li-Hui Xu; Dong-Yun Ouyang; Feng-Yi Mai; Qiong-Zhen Zeng; Cheng-Cheng Zhang; Rui-Man Li; Xian-Hui He (Apoptosis, 2019)

Diversification of mitogenomes in three sympatric Altica flea beetles (Insecta, Chrysomelidae) - Rui‐E Nie; Jing Wei; Shou‐Ke Zhang; Alfried P. Vogler; Ling Wu; Alexander S. Konstantinov; Wen‐Zhu Li; Xing‐Ke Yang; Huai‐Jun Xue (Zoologica Scripta, 2019)
The Asian flea beetles Altica cirsicola , Altica fragariae and Altica viridicyanea are broadly sympatric and morphologically highly similar but feed on distantly related host plants. They have been suggested as a model for ecological speciation studies. However, their phylogeny and species limits remain uncertain. In this study, we added mitochondrial genomes from multiple individuals of each species to the growing database. Phylogenetic analyses based on 15 genes showed clear interspecific divergences of A. fragariae from the other species, but A. cirsicola and A. viridicyanea were not distinguishable by distance‐based or tree‐based methods of species delimitation due to non‐monophyly of mitogenomes relative to the morphologically defined entities, possibly affected by interspecific introgression. This was confirmed by wider sampling of mitochondrial COX1 (58 individuals) and the second internal transcribed spacer of nuclear ribosomal RNA cluster (ITS2; 68 individuals), which showed that ITS2, but not COX1, coincided with the morphological species limits. The full mitochondrial genomes are not able to shed further light on the species status, even with the most sensitive approach based on diagnostic characters, yet the whole mitogenome is useful to get improved estimates of intra‐ and interspecific variation, not affected by the stochastic error seen in individual genes.

New Insights into Dose- and Time-Dependent Response of Five Typical PPCPs on Soil Microbial Respiration - Wenjie Zhang; Jun Wang; Jinhua Wang; Lusheng Zhu; Ning Lv; Rui Wang; Zulfiqar Ahmad (Bulletin of Environmental Contamination and Toxicology, 2019)

Growth Inhibiting Effects of Four Antibiotics on Cucumber, Rape and Chinese Cabbage - Rui Wang; Jun Wang; Jinhua Wang; Lusheng Zhu; Wenjie Zhang; Xiang Zhao; Zulfiqar Ahmad (Bulletin of Environmental Contamination and Toxicology, 2019)

Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2019)

Comparison of levofloxacin-based prophylaxis regimens for transrectal prostate biopsy: a prospective randomized single-center study - Rui Su; Kai-yun Wang; Dong Zhang; Ze-jun Yan; Jun-hui Jiang; Qi Ma (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Energy-Based Brittleness Index and Acoustic Emission Characteristics of Anisotropic Coal Under Triaxial Stress Condition - Jun Zhang; Chi Ai; Yu-wei Li; Ming-guang Che; Rui Gao; Jia Zeng (Rock Mechanics and Rock Engineering, 2018)

A Novel True Triaxial Apparatus for Studying the Time-Dependent Behaviour of Hard Rocks Under High Stress - Xia-Ting Feng; Jun Zhao; Xiwei Zhang; Rui Kong (Rock Mechanics and Rock Engineering, 2018)

Assessing the influence of climate change and inter-basin water diversion on Haihe River basin, eastern China: a coupled model approach - Jun Xia; Qiang Wang; Xiang Zhang; Rui Wang; Dunxian She (Hydrogeology Journal, 2018)

Identification of blasting vibration and coal-rock fracturing microseismic signals - Xing-Li Zhang; Rui-Sheng Jia; Xin-Ming Lu; Yan-Jun Peng; Wei-Dong Zhao (Applied Geophysics, 2018)

Effects of diurnal temperature range on mortality in Hefei city, China - Jing Tang; Chang-chun Xiao; Yu-rong Li; Jun-qing Zhang; Hao-yuan Zhai; Xi-ya Geng; Rui Ding; Jin-xia Zhai (International Journal of Biometeorology, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Effects of different C/N ratios on bacterial compositions and processes in an organically managed soil - Jun Ye; Pablo Gonzalez Perez; Rui Zhang; Shaun Nielsen; Danfeng Huang; Torsten Thomas (Biology and Fertility of Soils, 2018)

The higher grain production, the more social deprivation? A case study of Henan province in traditional agricultural areas of China - Jun-bo Gao; Wei-feng Qiao; Yan-sui Liu; Yu-rui Li; Wei Tu; Yong-xian Zhang (Journal of Mountain Science, 2018)

Photoperiodism dynamics during the domestication and improvement of soybean - Sheng-Rui Zhang; Huan Wang; Zhongyu Wang; Yao Ren; Lifang Niu; Jun Liu; Bin Liu (Science China Life Sciences, 2017)

Synthesis and biological evaluation of disulfides bearing 1,2,4-triazole moiety as antiproliferative agents - Xue-Feng Wang; Shuai Zhang; Bao-Lin Li; Ji-Jun Zhao; Yu-Ming Liu; Rui-Lian Zhang; Bo Li; Bao-Quan Chen (Medicinal Chemistry Research, 2017)

Thermal recovery process of a backfilled open-pit in permafrost area at the Gulian strip coal mine in Northeast China - Shu-hui Gao; Rui-xia He; Hui-jun Jin; Ya-dong Huang; Jian-ming Zhang; Dong-liang Luo (Journal of Mountain Science, 2017)

Populus euphratica J3 mediates root K+/Na+ homeostasis by activating plasma membrane H+-ATPase in transgenic Arabidopsis under NaCl salinity - Yinan Zhang; Yang Wang; Gang Sa; Yuhong Zhang; Jiayin Deng; Shurong Deng; Meijuan Wang; Huilong Zhang; Jun Yao; Xiuying Ma; Rui Zhao; Xiaoyang Zhou; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Tbx18-dependent differentiation of brown adipose tissue-derived stem cells toward cardiac pacemaker cells - Lei Chen; Zi-Jun Deng; Jian-Sheng Zhou; Rui-Juan Ji; Xi Zhang; Chuan-Sen Zhang; Yu-Quan Li; Xiang-Qun Yang (Molecular and Cellular Biochemistry, 2017)

Puerarin may protect against Schwann cell damage induced by glucose fluctuation - Bing Xue; Lin Wang; Zhe Zhang; Rui Wang; Xin-xin Xia; Ping-ping Han; Li-jun Cao; Yong-hui Liu; Lian-qing Sun (Journal of Natural Medicines, 2017)

Characterization and speciation of mercury in mosses and lichens from the high-altitude Tibetan Plateau - Jun-juan Shao; Cheng-bin Liu; Qing-hua Zhang; Jian-jie Fu; Rui-qiang Yang; Jian-bo Shi; Yong Cai; Gui-bin Jiang (Environmental Geochemistry and Health, 2017)

Rhizobium rhizosphaerae sp. nov., a novel species isolated from rice rhizosphere - Juan-Juan Zhao; Jun Zhang; Rui-Jie Zhang; Cai-Wen Zhang; Hua-Qun Yin; Xiao-Xia Zhang (Antonie van Leeuwenhoek, 2017)

Characterization of a neutral recombinant xylanase from Thermoactinospora rubra YIM 77501T - Yi-Rui Yin; Qing-Wen Hu; Wen-Dong Xian; Feng Zhang; En-Min Zhou; Hong Ming; Min Xiao; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2017)

Efficient Generation of Functionally Active Spinal Cord Neurons from Spermatogonial Stem Cells - Hao Yang; Cuicui Liu; Bo Chen; Jing An; Rui Zhang; Qian Zhang; Jingjing Zhao; Baorong He; Ding-Jun Hao (Molecular Neurobiology, 2017)

Paenibacillus oryzisoli sp. nov., isolated from the rhizosphere of rice - Jun Zhang; Xiao-Tong Ma; Jun-Sheng Gao; Cai-Wen Zhang; Juan-Juan Zhao; Rui-Jie Zhang; Li-An Ma; Xiao-Xia Zhang (Antonie van Leeuwenhoek, 2017)

MicroRNA-9 Mediates the Cell Apoptosis by Targeting Bcl2l11 in Ischemic Stroke - Na Wei; Lin Xiao; Rui Xue; Dandan Zhang; Jun Zhou; Huayan Ren; Si Guo; Jingjing Xu (Molecular Neurobiology, 2016)

Dissipation of excess excitation energy of the needle leaves in Pinus trees during cold winters - AO Zhang; Zhen-Hai Cui; Jia-Lin Yu; Zi-Ling Hu; Rui Ding; Da-Ming Ren; Li-Jun Zhang (International Journal of Biometeorology, 2016)

Thermal state of soils in the active layer and underlain permafrost at the kilometer post 304 site along the China-Russia Crude Oil Pipeline - Yong-ping Wang; Guo-yu Li; Hui-jun Jin; Lan-zhi Lu; Rui-xia He; Peng Zhang (Journal of Mountain Science, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Erythropoietin Attenuates the Memory Deficits in Aging Rats by Rescuing the Oxidative Stress and Inflammation and Promoting BDNF Releasing - Zhankui Jia; Rui Xue; Shengli Ma; Jingjing Xu; Si Guo; Songchao Li; Erwei Zhang; Jun Wang; Jinjian Yang (Molecular Neurobiology, 2016)

Cloning and molecular characterization of Myb transcription factors from Leymus (Poaceae: Trticeae) - Ying-xia Lei; Yan Zhang; Yang-yi Li; Jian-Jun Lai; Gang Gao; Hai-qin Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

Molecular cloning and characterization of the MsHSP17.7 gene from Medicago sativa L. - Zhen-yi Li; Rui-cai Long; Tie-jun Zhang; Qing-chuan Yang; Jun-mei Kang (Molecular Biology Reports, 2016)

A new flavane acid from the fruits of Illicium verum - Liang-Deng Wu; Chun-Lan Xiong; Zi-Zhan Chen; Rui-Jie He; Yan-Jun Zhang; Yan Huang; Sheng-Ping Deng; Rui-Yun Yang; Jun Li (Natural Product Research, 2016)

Muscle fiber types composition and type identified endplate morphology of forepaw intrinsic muscles in the rat - Feng Pan; Jing-yi Mi; Yan Zhang; Xiao-yun Pan; Yong-jun Rui (Journal of Muscle Research and Cell Motility, 2016)

Mechanism Underlying the Analgesic Effect Exerted by Endomorphin-1 in the rat Ventrolateral Periaqueductal Gray - Tao Chen; Jing Li; Ban Feng; Rui Hui; Yu-Lin Dong; Fu-Quan Huo; Ting Zhang; Jun-Bin Yin; Jian-Qing Du; Yun-Qing Li (Molecular Neurobiology, 2016)

Mutations in circularly permuted GTPase family genes AtNOA1/RIF1/SVR10 and BPG2 suppress var2-mediated leaf variegation in Arabidopsis thaliana - Yafei Qi; Jun Zhao; Rui An; Juan Zhang; Shuang Liang; Jingxia Shao; Xiayan Liu; Lijun An; Fei Yu (Photosynthesis Research, 2016)

Effect of abiotic stress on the gameophyte of Pyropia katadae var. hemiphylla (Bangiales, Rhodophyta) - Wen-Jun Wang; Xiu-Tao Sun; Fu-Li Liu; Zhou-Rui Liang; Ji-Hong Zhang; Fei-Jiu Wang (Journal of Applied Phycology, 2016)

Impact of climate change on regional irrigation water demand in Baojixia irrigation district of China - Xiao-jun Wang; Jian-yun Zhang; Mahtab Ali; Shamsuddin Shahid; Rui-min He; Xing-hui Xia; Zhuo Jiang (Mitigation and Adaptation Strategies for Global Change, 2016)

UV photolysis for enhanced phenol biodegradation in the presence of 2,4,6-trichlorophenol (TCP) - Jiaxiu Song; Wenbing Wang; Rongjie Li; Jun Zhu; Yongming Zhang; Rui Liu; Bruce E. Rittmann (Biodegradation, 2016)

Circulation and in vivo distribution of duck hepatitis A virus types 1 and 3 in infected ducklings - Shao-Li Lin; Ri-Chao Cong; Rui-Hua Zhang; Jun-Hao Chen; Lin-Lin Xia; Zhi-Jing Xie; Yu Wang; Yan-Li Zhu; Shi-Jin Jiang (Archives of Virology, 2016)

Adaptation to climate change impacts on water demand - Xiao-jun Wang; Jian-yun Zhang; Shamsuddin Shahid; En-hong Guan; Yong-xiang Wu; Juan Gao; Rui-min He (Mitigation and Adaptation Strategies for Global Change, 2016)

Curcumin Promotes Cell Cycle Arrest and Inhibits Survival of Human Renal Cancer Cells by Negative Modulation of the PI3K/AKT Signaling Pathway - Hao Zhang; Weili Xu; Baolin Li; Kai Zhang; Yudong Wu; Haidong Xu; Junyong Wang; Jun Zhang; Rui Fan; Jinxing Wei (Cell Biochemistry and Biophysics, 2015)

Distribution of the Vrn-D1b allele associated with facultative growth habit in Chinese wheat accessions - Xian-rui Guo; Yuan-yuan Wang; Ling-zhi Meng; Hong-wei Liu; Li Yang; Yang Zhou; Hong-jun Zhang (Euphytica, 2015)

Molecular cloning and characterization of caffeic acid 3-O-methyltransferase from the rhizome of Ligusticum chuanxiong - Juan-Juan Li; Gan Zhang; Ji-hua Yu; Yang-yang Li; Xin-he Huang; Wan-Jun Wang; Rui Tan; Jia-yu Zhou; Hai Liao (Biotechnology Letters, 2015)

Umezawaea endophytica sp. nov., isolated from tobacco root samples - Xiao Chu; Bing-Bing Liu; Rui Gao; Zheng-Yu Zhang; Yan-Qing Duan; Salam Nimaichand; Wei Chen; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

The concentration of selenium matters: a field study on mercury accumulation in rice by selenite treatment in qingzhen, Guizhou, China - Yu-Feng Li; Jiating Zhao; Yunyun Li; Hanjun Li; Junfang Zhang; Bai Li; Yuxi Gao; Chunying Chen; Manyi Luo; Rui Huang; Jun Li (Plant and Soil, 2015)

Decreased expression of microRNA-125a-3p upregulates interleukin-23 receptor in patients with Hashimoto’s thyroiditis - Huiyong Peng; Yingzhao Liu; Jie Tian; Jie Ma; Xinyi Tang; Jun Yang; Ke Rui; Yue Zhang; Chaoming Mao; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2015)

Effect of the CYP2D6 gene polymorphism on postoperative analgesia of tramadol in Han nationality nephrectomy patients - Hong Dong; Shu-jun Lu; Rui Zhang; Dong-dong Liu; Yan-zhuo Zhang; Chun-yu Song (European Journal of Clinical Pharmacology, 2015)

A simple and rapid approach to manipulate pseudorabies virus genome by CRISPR/Cas9 system - Aotian Xu; Chao Qin; Yue Lang; Mingyue Wang; Mengyang Lin; Chuang Li; Rui Zhang; Jun Tang (Biotechnology Letters, 2015)

MiR-1224-5p acts as a tumor suppressor by targeting CREB1 in malignant gliomas - Jin Qian; Rui Li; Ying-Yi Wang; Yan Shi; Wen-Kang Luan; Tao Tao; Jun-Xia Zhang; Yi-Chang Xu; Yong-Ping You (Molecular and Cellular Biochemistry, 2015)

Rhodococcus agglutinans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Ling Meng; Yan-Yan Duan; Rui Gao; Jian-Xin Zhang; Jian-Rong Huang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

Characterization of the amino acid composition of soils under organic and conventional management after addition of different fertilizers - Pablo Gonzalez Perez; Rui Zhang; Xiaoli Wang; Jun Ye; Danfeng Huang (Journal of Soils and Sediments, 2015)

Heterologous expression and characterization of a novel halotolerant, thermostable, and alkali-stable GH6 endoglucanase from Thermobifida halotolerans - Yi-Rui Yin; Feng Zhang; Qing-Wen Hu; Wen-Dong Xian; Wael N. Hozzein; En-Min Zhou; Hong Ming; Guo-Xing Nie; Wen-Jun Li (Biotechnology Letters, 2015)

Historic water consumptions and future management strategies for Haihe River basin of Northern China - Xiao-jun Wang; Jian-yun Zhang; Zhi-feng Yang; Shamsuddin Shahid; Rui-min He; Xing-hui Xia; Hong-wei Liu (Mitigation and Adaptation Strategies for Global Change, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Potential impact of climate change on future water demand in Yulin city, Northwest China - Wang Xiao-jun; Zhang Jian-yun; Shahid Shamsuddin; He Rui-min; Xia Xing-hui; Mou Xin-li (Mitigation and Adaptation Strategies for Global Change, 2015)

Association of microRNA-3144 variant with the susceptibility to hepatocellular carcinoma - Jun Zhang; Rui Wang; Min Cai; Shunji Yu; Yanyun Ma; Weihong Xu; Chunfang Gao; Jiucun Wang; Lifang Hou; Yi Liu; Jie Liu (Genes & Genomics, 2014)

Snail regulated by PKC/GSK-3β pathway is crucial for EGF-induced epithelial-mesenchymal transition (EMT) of cancer cells - Zong-cai Liu; Xiao-hui Chen; Hai-xing Song; Hong-sheng Wang; Ge Zhang; Hao Wang; Dan-yang Chen; Rui Fang; Hao Liu; Shao-hui Cai; Jun Du (Cell and Tissue Research, 2014)

Distance effect of matrix attachment regions on transgene expression in stably transfected Chinese hamster ovary cells - Jun-He Zhang; Xiao-Yin Wang; Tian-Yun Wang; Fang Wang; Wei-Hua Dong; Li Wang; Chun-Peng Zhao; Shu-Jie Chai; Rui Yang; Qin Li (Biotechnology Letters, 2014)

Chemical constituents from Melastoma dodecandrum and their inhibitory activity on interleukin-8 production in HT-29 cells - Guo-Xun Yang; Rui-Ze Zhang; Bin Lou; Ke-Jun Cheng; Juan Xiong; Jin-Feng Hu (Natural Product Research, 2014)

Streptomyces calidiresistens sp. nov., isolated from a hot spring sediment - Yan-Yan Duan; Hong Ming; Lei Dong; Yi-Rui Yin; Yi Zhang; En-Min Zhou; Lan Liu; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Precise and Economical Dredging Model of Sediments and Its Field Application: Case Study of a River Heavily Polluted by Organic Matter, Nitrogen, and Phosphorus - Rui Zhang; Fan-Xin Zeng; Wu-Jun Liu; Raymond J. Zeng; Hong Jiang (Environmental Management, 2014)

The metabolism of 8-heptadecene in Pyropia (Bangiaceae, Rhodophyta) - Min Zhang; Rui-Xia Li; Chuan-Ming Hu; Li-En Yang; Jun Tang; Qin-Qin Lu; Tao Zhang; Zong-Gen Shen; Song-Dong Shen; Pu Xu; Jian-Yi Zhu (Journal of Applied Phycology, 2014)

Catastrophe theory to assess water security and adaptation strategy in the context of environmental change - Wang Xiao-jun; Zhang Jian-yun; Shamsuddin Shahid; Xia Xing-hui; He Rui-min; Shang Man-ting (Mitigation and Adaptation Strategies for Global Change, 2014)

Pollen morphology and its phylogenetic implications in the genus Picea - Zi Rui Jia; Jun Hui Wang; Shou Gong Zhang (Plant Systematics and Evolution, 2014)

Mechanism and comprehensive countermeasure for drought management from the view of catastrophe theory - Xiao-jun Wang; Jian-yun Zhang; Xue-wei Tong; Shahid Shamsuddin; Rui-min He; Xing-hui Xia (Natural Hazards, 2014)

Soluble N-terminal fragment of mutant Huntingtin protein impairs mitochondrial axonal transport in cultured hippocampal neurons - Jun Tian; Ya-Ping Yan; Rui Zhou; Hui-Fang Lou; Ye Rong; Bao-Rong Zhang (Neuroscience Bulletin, 2014)

Spatial and temporal plasticity of synaptic organization in anterior cingulate cortex following peripheral inflammatory pain: multi-electrode array recordings in rats - Yun-Fei Lu; Yan Wang; Ying He; Fu-Kang Zhang; Ting He; Rui-Rui Wang; Xue-Feng Chen; Fei Yang; Ke-Rui Gong; Jun Chen (Neuroscience Bulletin, 2014)

Phytoremediation potential of Pteris vittata L. under the combined contamination of As and Pb: beneficial interaction between As and Pb - Xiao-ming Wan; Mei Lei; Tong-bin Chen; Guang-dong Zhou; Jun Yang; Xiao-yong Zhou; Xi Zhang; Rui-xiang Xu (Environmental Science and Pollution Research, 2014)

Climate change and water resources management in Tuwei river basin of Northwest China - Wang Xiao-jun; Zhang Jian-yun; Wang Jian-hua; He Rui-min; Amgad ElMahdi; Liu Jin-hua; Wang Xin-gong; David King; Shamsuddin Shahid (Mitigation and Adaptation Strategies for Global Change, 2014)

Effect of sulphate nutrition on arsenic translocation and photosynthesis of rice seedlings - Rui Song; Chen-Yun Zhao; Juan Liu; Jing Zhang; Yan-Xiu Du; Jun-Zhou Li; Hong-Zheng Sun; Hong-Bing Zhao; Quan-Zhi Zhao (Acta Physiologiae Plantarum, 2013)

Transcriptome profiling and digital gene expression analysis of Nile tilapia (Oreochromis niloticus) infected by Streptococcus agalactiae - Rui Zhang; Li-li Zhang; Xing Ye; Yuan-yuan Tian; Cheng-fei Sun; Mai-xin Lu; Jun-jie Bai (Molecular Biology Reports, 2013)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

Evaluation of salinity tolerance in seedlings of sugar beet (Beta vulgaris L.) cultivars using proline, soluble sugars and cation accumulation criteria - Guo-Qiang Wu; Na Liang; Rui-Jun Feng; Jing-Jing Zhang (Acta Physiologiae Plantarum, 2013)

A new sesquiterpene lactone from Sarcandra glabra - Xiao-Ru Hu; Hai-Feng Wu; Xiao-Po Zhang; Jun-Shan Yang; Zhong Dai; Rui-Chao Lin; Xu-Dong Xu (Natural Product Research, 2013)

An AFLP, SRAP, and SSR Genetic Linkage Map and Identification of QTLs for Fruit Traits in Pear (Pyrus L.) - Rui-ping Zhang; Jun Wu; Xiu-gen Li; M. Awais Khan; Hui Chen; Schuyler S. Korban; Shao-ling Zhang (Plant Molecular Biology Reporter, 2013)

Meso-Cenozoic extensional structures in the Northern Tarim Basin, NW China - Yue-Jun Li; Yan Zhao; Long-De Sun; Wen-Jie Song; Duo-Ming Zheng; Ya-Lei Liu; Dao-Xuan Wang; Jian-Feng Hu; Qi-Rui Zhang (International Journal of Earth Sciences, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Metal-Binding Activity of the Soluble Recombinant Pig Metallothionein 1A Expressed in Escherichia coli - Dongbo Sun; Hong Zhang; Guojun Wu; Qinghe Zhu; Siwen Lv; Donghua Guo; Rui Wu; Jun Bao (Biological Trace Element Research, 2012)

Water resources management strategy for adaptation to droughts in China - Wang Xiao-jun; Zhang Jian-yun; Shamsuddin Shahid; Amgad ElMahdi; He Rui-min; Bao Zhen-xin; Mahtab Ali (Mitigation and Adaptation Strategies for Global Change, 2012)

Does glyphosate impact on Cu uptake by, and toxicity to, the earthworm Eisenia fetida? - Chui-Fan Zhou; Yu-Jun Wang; Yuan-Chun Yu; Rui-Juan Sun; Xiang-Dong Zhu; Hai-Lin Zhang; Dong-Mei Zhou (Ecotoxicology, 2012)

Lihuaxuella thermophila gen. nov., sp. nov., isolated from a geothermal soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Bing-Huo Zhang; Ji-Cheng Yao; Shu-Kun Tang; En-Min Zhou; Yi-Rui Yin; Da-Qiao Wei; Hong Ming; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

Dynamics and functions of CD4+CD25high regulatory T lymphocytes in Chinese rhesus macaques during the early stage of infection with SIVmac239 - Shao-You Li; Hou-Jun Xia; Zheng-Xi Dai; Gao-Hong Zhang; Bo Fan; Ming-Hua Li; Rui-Rui Wang; Yong-Tang Zheng (Archives of Virology, 2012)

Effects of a non-selective TRPC channel blocker, SKF-96365, on melittininduced spontaneous persistent nociception and inflammatory pain hypersensitivity - Jing Ding; Jia-Rui Zhang; Yan Wang; Chun-Li Li; Dan Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2012)

Purification and partial characterization of glutathione S-transferases from three field populations of Panonychus citri (Acari: Tetranychidae) - Jin-Zhi Niu; Wei Dou; Bao-Jun Wang; Guo-Na Zhang; Rui Zhang; Yi Yin; Jin-Jun Wang (Experimental and Applied Acarology, 2012)

Gini coefficient to assess equity in domestic water supply in the Yellow River - Xiao-jun Wang; Jian-yun Zhang; Shamsuddin Shahid; Amgad ElMahdi; Rui-min He; Xin-gong Wang; Mahtab Ali (Mitigation and Adaptation Strategies for Global Change, 2012)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

Induction of lactadherin mediates the apoptosis of endothelial cells in response to advanced glycation end products and protective effects of grape seed procyanidin B2 and resveratrol - Bao-ying Li; Xiao-li Li; Qian Cai; Hai-qing Gao; Mei Cheng; Jian-hua Zhang; Jun-fu Wang; Fei Yu; Rui-hai Zhou (Apoptosis, 2011)

The cardioprotective effect of fluvastatin on ischemic injury via down-regulation of toll-like receptor 4 - Jun Yang; Xiao-Dong Zhang; Jian Yang; Jia-Wang Ding; Zhao-Qi Liu; Shu-Guo Li; Rui Yang (Molecular Biology Reports, 2011)

Risk of high-grade bleeding in patients with cancer treated with bevacizumab: a meta-analysis of randomized controlled trials - Xiao Feng Hang; Wen Sheng Xu; Jun Xue Wang; Lei Wang; Hai Guang Xin; Rui Qi Zhang; Wu Ni (European Journal of Clinical Pharmacology, 2011)

A strategy to deal with water crisis under climate change for mainstream in the middle reaches of Yellow River - Xiao-jun Wang; Jian-yun Zhang; Rui-min He; ElMahdi Amgad; ElSawah Sondoss; Man-ting Shang (Mitigation and Adaptation Strategies for Global Change, 2011)

Water resources planning and management based on system dynamics: a case study of Yulin city - Xiao-jun Wang; Jian-yun Zhang; Jiu-fu Liu; Guo-qing Wang; Rui-min He; Amgad Elmahdi; Sondoss Elsawah (Environment, Development and Sustainability, 2011)

Synthesis, Crystal Structure, Interaction with BSA and Antibacterial Activity of La(III) and Sm(III) Complexes with Enrofloxacin - Yan-Jun Wang; Rui-Ding Hu; Dong-Hua Jiang; Ping-Hua Zhang; Qiu-Yue Lin; Yun-Yun Wang (Journal of Fluorescence, 2011)

Development of Juglans Regia SSR Markers by Data Mining of the EST Database - Rui Zhang; AnDan Zhu; XinJian Wang; Jun Yu; HongRong Zhang; JiangSheng Gao; YunJiang Cheng; XiuXin Deng (Plant Molecular Biology Reporter, 2010)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

RETRACTED ARTICLE: Cytotoxic activities of tubeimoside-2 on human hepatoma HepG2 cells by induction of G2/M phase arrest and apoptosis in a p53-dependent manner - Ying-Yong Zhao; Xu Chao; Yongmin Zhang; Li-Jun Sun; Hong Zhang; Rui-Chao Lin; Xuefeng Shen; Wen-Ji Sun (Apoptosis, 2010)

The formation and evolution of Chepaizi-Mosuowan paleo-uplift and its control on the distributions of sedimentary facies in the Junggar Basin - YouLiang Ji; Yong Zhou; Jun Kuang; Lu Wan; Rui Zhang; ChunHong Lu (Science China Earth Sciences, 2010)

Photocatalytic degradation of organic dyes by Er3+:YAlO3/TiO2 composite under solar light - Jun Wang; Yingpeng Xie; Zhaohong Zhang; Jia Li; Chengwu Li; Liquan Zhang; Zhiqiang Xing; Rui Xu; Xiangdong Zhang (Environmental Chemistry Letters, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Dynamics of soil properties and organic carbon pool in topsoil of zokor-made mounds at an alpine site of the Qinghai–Tibetan Plateau - Xiao Gang Li; Mei Lan Zhang; Zhuo Ting Li; Xiao Ming Shi; Qifu Ma; Rui Jun Long (Biology and Fertility of Soils, 2009)

A novel triple-regulated oncolytic adenovirus carrying PDCD5 gene exerts potent antitumor efficacy on common human leukemic cell lines - Min Xie; Ji-Hong Niu; Yan Chang; Qi-Jun Qian; Hong-Ping Wu; Lin-Fang Li; Yao Zhang; Jin-Lan Li; Xiao-Jun Huang; Guo-Rui Ruan (Apoptosis, 2009)

Angiotensin II upregulates Toll-like receptor 4 and enhances lipopolysaccharide-induced CD40 expression in rat peritoneal mesothelial cells - Jun Wu; Xiao Yang; Yun-Fang Zhang; Shu-Feng Zhou; Rui Zhang; Xiu-Qing Dong; Jin-Jin Fan; Mei Liu; Xue-Qing Yu (Inflammation Research, 2009)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

Expression of thyrotropin-releasing hormone receptors in rat testis and their role in isolated Leydig cells - Yong Zhao; Wu-Gang Hou; Hua-Ping Zhu; Jie Zhao; Rui-An Wang; Ruo-Jun Xu; Yuan-Qiang Zhang (Cell and Tissue Research, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

Degradation of Hazardous Dyes in Wastewater using Nanometer Mixed Crystal TiO2 Powders under Visible Light Irradiation - Jun Wang; Ronghe Li; Zhaohong Zhang; Wei Sun; Xiaofang Wang; Rui Xu; Zhiqiang Xing; Xiangdong Zhang (Water, Air, & Soil Pollution, 2008)

Spatial distributions of organic carbon and nitrogen and their isotopic compositions in sediments of the Changjiang Estuary and its adjacent sea area - Jianhua Gao; Yaping Wang; Shaoming Pan; Rui Zhang; Jun Li; Fenglong Bai (Journal of Geographical Sciences, 2008)

Molecular cloning and characterization of two novel cellulase genes from the mollusc Ampullaria crossean - Rui Guo; Ming Ding; Si-Liang Zhang; Gen-jun Xu; Fu-kun Zhao (Journal of Comparative Physiology B, 2008)

Insulin inhibits β-adrenergic action in ischemic/reperfused heart: a novel mechanism of insulin in cardioprotection - Qiu-Jun Yu; Rui Si; Ning Zhou; Hai-Feng Zhang; Wen-Yi Guo; Hai-Chang Wang; Feng Gao (Apoptosis, 2008)

An experimental study of the mechanisms of freeze/thaw and wind erosion of ancient adobe buildings in northwest China - Jian-Jun Qu; Guo-Dong Cheng; Ke-Cun Zhang; Jia-Cheng Wang; Rui-Ping Zu; Hai-Yan Fang (Bulletin of Engineering Geology and the Environment, 2007)

Polymorphism of the mouse gene for the interleukin 10 receptor alpha chain (Il10ra) and its association with the autoimmune phenotype - Zan-Mei Qi; Jun Wang; Zheng-Rong Sun; Feng-Mao Ma; Qing-Rui Zhang; Sachiko Hirose; Yi Jiang (Immunogenetics, 2005)

Biophysical studies of a ruthenium(II) polypyridyl complex binding to DNA and RNA prove that nucleic acid structure has significant effects on binding behaviors - Hong Xu; Yi Liang; Peng Zhang; Fen Du; Bing-Rui Zhou; Jun Wu; Jian-Hong Liu; Zhi-Gang Liu; Liang-Nian Ji (JBIC Journal of Biological Inorganic Chemistry, 2005)

Study on construction of cDNA libraries from rat normal liver and regeneration liver with smart technique - Lin Jun-Tang; Wang Cong-Rui; Jogenananda Pramanik; Zhang Hui-Yong; Feng Hui-Gen; Yang Bao-Sheng; L. I. Yu-Chang; Xu Cun-Shuan (Indian Journal of Clinical Biochemistry, 2004)

Crystal structure studies on rubrerythrin: enzymatic activity in relation to the zinc movement - Mei Li; Ming-yih Liu; Jean LeGall; Lu-lu Gui; Jun Liao; Tao Jiang; Ji-ping Zhang; Dong-cai Liang; Wen-rui Chang (JBIC Journal of Biological Inorganic Chemistry, 2003)

Research progress of socio-economic water cycle in China - Jia Shao-feng; Wang Guo; Zhang Shi-feng; Yu Gui-rui; Wang Jin-xia; Xia Jun (Journal of Geographical Sciences, 2002)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)